Lithium precipitation mother liquor recovery method, composite ferrous sulfate sodium material, positive electrode sheet, and secondary battery

By adjusting the pH value of the lithium precipitation mother liquor and calcining treatment, combined with carbon coating technology, lithium ions and sodium ions were successfully separated and recovered, solving the problems of resource waste and environmental pollution in existing technologies. High-performance composite sodium ferrous sulfate material was prepared, improving the performance of secondary batteries.

CN121020660BActive Publication Date: 2026-03-17HUBEI WANRUN NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511530420.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-24
Publication Date
2026-03-17
Estimated Expiration
2045-10-24

AI Technical Summary

Technical Problem

Existing technologies are unable to effectively separate and recycle lithium ions and sodium ions, leading to resource waste and environmental pollution. Furthermore, traditional processes are energy-intensive and lengthy.

Method used

By adjusting the pH of the lithium precipitation mother liquor to less than or equal to 5, adding ferrous sulfate and sodium salt, and then drying and calcining, a water-insoluble sodium ferrous sulfate precursor is generated. After pulverizing, it is mixed with a reducing agent to separate lithium ions. Then, a carbon source and reducing agent are added for grinding and calcination to form a carbon-coated composite sodium ferrous sulfate material.

Benefits of technology

This method achieves efficient separation of lithium ions and sodium ions, improves element recovery rate, and yields high-purity and high-capacity composite sodium ferrous sulfate material, thereby enhancing the performance of secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121020660B_ABST
    Figure CN121020660B_ABST
Patent Text Reader

Abstract

The application provides a lithium precipitation mother liquor recovery method, a composite ferrous sulfate sodium material, a positive electrode sheet and a secondary battery, and belongs to the secondary battery field, wherein the lithium precipitation mother liquor recovery method comprises the following steps: adjusting the pH value of the lithium precipitation mother liquor to be less than or equal to 5 to obtain a first mother liquor; the first mother liquor is mixed with ferrous sulfate, a sodium salt and a first reducing agent; the first mixture is subjected to a first drying treatment; the first dried material is subjected to a first calcination treatment to obtain a first calcined material; the first calcined material is subjected to a crushing treatment to obtain a crushed material; after the crushed material is mixed with an aqueous solution of a second reducing agent and is subjected to a solid-liquid separation treatment, a ferrous sulfate sodium precursor is obtained; the ferrous sulfate sodium precursor is subjected to a slurry treatment to obtain a first slurry; after the first slurry, a carbon source and a third reducing agent are mixed, the mixture is subjected to a grinding treatment, a second drying treatment and a second calcination treatment to obtain a composite ferrous sulfate sodium material. The application is beneficial to realizing effective separation of lithium ions and sodium ions in the lithium precipitation mother liquor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of secondary battery technology, specifically to a method for recovering lithium precipitation mother liquor, a composite sodium ferrous sulfate material and its preparation method, a positive electrode sheet, and a secondary battery. Background Technology

[0002] In the production of lithium-ion and sodium-ion batteries, the lithium precipitation mother liquor, which is produced after extracting lithium carbonate from lithium ore, is a waste product rich in various valuable elements. Lithium precipitation mother liquor is typically alkaline and mainly consists of high concentrations of sodium ions, sulfate ions, lithium ions, and small amounts of transition metals such as iron. If left untreated, it will lead to resource waste and environmental problems.

[0003] Currently, the industry commonly uses freeze crystallization to treat lithium precipitation mother liquor, precipitating sodium sulfate, followed by evaporation and concentration to precipitate lithium carbonate, and then recycling the precipitate. While this traditional process can recover some sodium sulfate, it suffers from high energy consumption, a long process time, and the return of some sodium to the system, leading to continuous enrichment of sodium and high sodium content in lithium carbonate, making it difficult to effectively separate sodium and lithium. Therefore, developing a method to effectively separate and recover lithium, sodium, and other elements from lithium precipitation mother liquor is of great significance. Summary of the Invention

[0004] In view of the technical problems existing in the background art, this application provides a method for recovering lithium precipitation mother liquor, a composite sodium ferrous sulfate material, a positive electrode sheet and a secondary battery, aiming to solve the technical problem that it is difficult to effectively separate sodium and lithium elements in the prior art.

[0005] In a first aspect, embodiments of this application provide a method for recovering lithium precipitation mother liquor, comprising the following steps:

[0006] Adjust the pH of the lithium precipitation mother liquor to less than or equal to 5 to obtain the first mother liquor;

[0007] The first mother liquor is mixed with ferrous sulfate, sodium salt and the first reducing agent to obtain the first mixture;

[0008] The first mixture undergoes a first drying process to obtain a first dried material;

[0009] The first dried material undergoes a first calcination process to obtain the first calcined material;

[0010] The first calcined material was pulverized to obtain pulverized material;

[0011] After the pulverized material is mixed with an aqueous solution of the second reducing agent, it is subjected to solid-liquid separation to obtain sodium ferrous sulfate precursor.

[0012] The sodium ferrous sulfate precursor was subjected to pulping treatment to obtain the first pulp;

[0013] The first slurry, carbon source, and third reducing agent are mixed and then ground to obtain the second slurry;

[0014] The second slurry undergoes a second drying process to obtain the second dried material;

[0015] The second dried material was subjected to a second calcination treatment to obtain a composite sodium ferrous sulfate material;

[0016] The molar ratio of sodium, iron and sulfate in the first mixture is (2.05-2.10):1:(2.02-2.10).

[0017] In the technical solution of this application embodiment, the pH value of the lithium precipitation mother liquor is adjusted to be less than or equal to 5. Using sulfate and sodium ions in the lithium precipitation mother liquor as sulfate and sodium ion sources, ferrous sulfate is first added to the lithium precipitation mother liquor as an iron source, followed by drying and calcination to obtain a first calcined material containing sodium ferrous sulfate precursor. The sodium ferrous sulfate precursor generated after calcination is poorly soluble in water. Furthermore, during the aforementioned drying and calcination process, lithium ions do not participate in the reaction and therefore exist in the sodium ferrous sulfate precursor in the form of lithium ions, which are easily washed out by water. By pulverizing the first calcined material, the pulverized material is mixed with an aqueous solution of a second reducing agent, and solid-liquid separation is performed to effectively separate lithium ions, obtaining a high-purity sodium ferrous sulfate precursor. Then, the sodium ferrous sulfate precursor is subjected to slurry treatment, supplemented with carbon source and third reducing agent, and then ground, dried and calcined. The carbon source is carbonized at high temperature and the sodium ferrous sulfate is coated with carbon in situ. The third reducing agent avoids the oxidation of ferrous ions during the grinding and drying process, which is conducive to obtaining high-purity and high-capacity composite sodium ferrous sulfate material. The process is simple and the recovery rate of elements such as sodium, iron and sulfur is high.

[0018] In some embodiments, the first mixture further includes a dopant selected from at least one of boric acid, phosphoric acid, silicic acid, and pyrophosphate, wherein the molar ratio of the dopant to sodium in the first mixture is (0.05 to 0.1):1.

[0019] In the above embodiments, by adding the aforementioned dopants (boric acid, phosphoric acid, silicic acid, pyrophosphate, etc.) and precisely controlling their molar ratio with sodium, it is beneficial to improve the electrochemical performance of the composite sodium ferrous sulfate material as a cathode material, such as capacity, cycle stability, and coulombic efficiency.

[0020] In some embodiments, the step of adjusting the pH of the lithium precipitation mother liquor to less than or equal to 5 includes:

[0021] Add sulfuric acid solution to the lithium precipitation mother liquor until the pH value of the lithium precipitation mother liquor is 2 to 5.

[0022] The aforementioned pH conditions are conducive to the formation of a structurally stable sodium ferrous sulfate precursor, improving the recovery rates of elements such as sodium, iron, and sulfur, and enhancing the separation efficiency of sodium and lithium. Furthermore, using a sulfuric acid solution to adjust the pH value provides a partial source of sulfuric acid and reduces the introduction of impurities, which is beneficial for obtaining high-purity composite sodium ferrous sulfate materials. Specifically, the sulfuric acid solution can be selected from commercially available concentrated sulfuric acid or an aqueous solution of sulfuric acid obtained by diluting concentrated sulfuric acid.

[0023] In some embodiments, the step of obtaining a first calcined material by first calcination of the first dried material includes:

[0024] The first dried material is subjected to a first protective atmosphere and a first calcination temperature, and then subjected to a first calcination time to obtain a first calcined material; wherein the first protective atmosphere is selected from one or more of nitrogen atmosphere, carbon dioxide atmosphere, and argon atmosphere, the first calcination temperature is 300℃ to 400℃, and the first calcination time is 10h to 20h.

[0025] In the above embodiments, high-temperature calcination under the protection of a protective gas effectively prevents the oxidation of ferrous ions, which is beneficial to improving the structural stability and purity of the obtained composite sodium ferrous sulfate material. Furthermore, the aforementioned first calcination temperature and first calcination time contribute to the uniform and complete crystallization of the sodium ferrous sulfate precursor in the first calcined material, facilitating the subsequent thorough washing and removal of lithium ions, high-yield recovery of elements such as sodium, iron, and sulfur, and obtaining a composite sodium ferrous sulfate material with excellent electrochemical performance.

[0026] In some embodiments, the step of mixing the pulverized material with an aqueous solution of a second reducing agent, followed by solid-liquid separation to obtain a sodium ferrous sulfate precursor includes:

[0027] The pulverized material is mixed with an aqueous solution of a second reducing agent, and after a first mixing temperature and a first mixing time, a second mixture is obtained.

[0028] The second mixture was separated into solid and liquid components to obtain solid material. The solid material was washed until the conductivity of the wash water was less than or equal to 300 μS / cm to obtain sodium ferrous sulfate precursor.

[0029] The first mixing time is 1 to 3 hours, and the first mixing temperature is 40°C to 80°C.

[0030] In the above embodiments, mixing the pulverized material with the aqueous solution of the second reducing agent at a first mixing temperature (40°C to 80°C) for a first mixing time (1h to 3h) is beneficial to fully dissolve impurity ions such as lithium ions in the pulverized material to obtain a second mixture. The second mixture is then subjected to solid-liquid separation and further washing to obtain a high-purity sodium ferrous sulfate precursor.

[0031] In some embodiments, the step of subjecting the second dried material to a second calcination treatment to obtain the composite sodium ferrous sulfate material includes:

[0032] The second drying material is subjected to a second protective atmosphere and a second calcination temperature, and then subjected to a second calcination time to obtain a composite sodium ferrous sulfate material; wherein, the second protective atmosphere is selected from one or more of nitrogen atmosphere, carbon dioxide atmosphere, and argon atmosphere, the second calcination temperature is 300℃ to 350℃, and the second calcination time is 6h to 12h.

[0033] In the above embodiments, the second calcination treatment under a second protective atmosphere facilitates the full reaction of the components in the second dried material at high temperatures, helps improve the crystal structure of the sodium ferrous sulfate material, and promotes the full doping of the dopant elements in the dopant, thereby improving the electrochemical performance of the composite sodium ferrous sulfate material. Furthermore, calcination at the second calcination temperature (300℃ to 350℃) for a second calcination time (6h to 12h) ensures sufficient high-temperature carbonization of the carbon source, forming a carbon coating layer. This effectively enhances the electronic conductivity of the composite sodium ferrous sulfate material and reduces its internal resistance. The composite sodium ferrous sulfate material prepared through this second calcination treatment exhibits good electronic and ionic conductivity, which is beneficial for improving the coulombic efficiency, capacity, and other electrochemical properties of the composite sodium ferrous sulfate material.

[0034] In some embodiments, the lithium precipitation mother liquor recovery method further includes:

[0035] The first filtrate obtained after solid-liquid separation of the second mixture is mixed with the washing water after washing the solid material to obtain a lithium-containing washing solution. The pH value of the lithium-containing washing solution is adjusted to 9 to 10.5 to obtain a lithium-containing solution. The lithium-containing solution is mixed with sodium phosphate to obtain a third mixture. The third mixture is then subjected to solid-liquid separation to obtain lithium phosphate.

[0036] In the above embodiments, the first filtrate and the washing water contain a high concentration of lithium ions. After mixing the two, they are mixed with sodium phosphate to obtain lithium phosphate, thus achieving the separation and recovery of lithium ions in the lithium precipitation mother liquor. The small amount of sodium ions, sulfate ions, and lithium ions remaining in the filtrate obtained after solid-liquid separation of the third mixture can be reused in the lithium precipitation mother liquor for recycling.

[0037] In some embodiments, the molar ratio of sodium phosphate to lithium in the lithium-containing solution is 1:(2.7-2.9), which is beneficial for the full precipitation of lithium.

[0038] In some embodiments, the step of mixing a lithium-containing solution with sodium phosphate to obtain a third mixture, and then separating the third mixture to obtain lithium phosphate, includes:

[0039] Sodium phosphate was added to a lithium-containing solution at 60°C to 90°C and stirred for 1 to 2 hours to obtain a third mixture. The filter residue obtained by solid-liquid separation of the third mixture was washed and dried to obtain lithium phosphate.

[0040] In the above embodiments, under the aforementioned temperature and time conditions, it is advantageous to obtain lithium phosphate with high yield and high purity, thereby achieving efficient and full recovery of lithium.

[0041] In some embodiments, the second calcination treatment further includes:

[0042] The calcined material obtained by calcining the second dried material under a second protective atmosphere and a second calcination temperature for a second calcination time is cooled to a temperature less than or equal to 100°C to obtain a cooled material.

[0043] The cooled material is sequentially screened and iron removed to obtain a composite sodium ferrous sulfate material.

[0044] In the above embodiments, by precisely controlling the cooling, sieving, and iron removal processes of the calcined material, the purity, dimensional consistency, and electrochemical performance of the composite sodium ferrous sulfate material can be improved, which is beneficial for the preparation of high-performance secondary batteries.

[0045] In some embodiments, the molar ratio of the first reducing agent to the iron element in the first mixture is (0.05 to 0.1):1.

[0046] In the above embodiments, the molar ratio of the first reducing agent to the iron element in the first mixture is within the above range, which helps to reduce the oxidation of ferrous ions in the subsequent mixing, drying and calcination processes, improve the purity and structural stability of the sodium ferrous sulfate precursor obtained from the first calcined material, facilitate the reduction of iron element contamination during the washing and removal of lithium ions, and improve the purity of the prepared composite sodium ferrous sulfate material.

[0047] In some embodiments, the first drying process and the second drying process are each independently performed using spray drying.

[0048] In the above embodiments, spray drying helps control the particle size of the first and second dried materials, which is beneficial to improving the electrochemical activity and ion transport capacity of the composite sodium ferrous sulfate material. In addition, as a highly efficient and rapid drying method, spray drying can significantly shorten drying time, reduce energy consumption, improve production efficiency, and is suitable for continuous large-scale production.

[0049] In some embodiments, the D50 particle size of the first dried material is 5 μm to 15 μm.

[0050] In the above embodiments, the D50 particle size of the first dried material is within the above range, which helps to obtain a first calcined material with concentrated particle size and uniform composition by utilizing the first calcination treatment, thereby improving the purity of the obtained sodium ferrous sulfate precursor.

[0051] In some embodiments, the water content in the first dried material is less than 1.5% by weight.

[0052] In the above embodiments, the first drying treatment removes moisture from the first mixture, reducing the impact of moisture on the material structure of the first calcined material during the subsequent high-temperature calcination process. Controlling the moisture content of the first dried material to below 1.5% helps reduce the shrinkage and pore structure damage caused by moisture, improving the structural stability of the first calcined material, thereby enhancing the regularity and stability of the structure of the subsequently prepared composite sodium ferrous sulfate material.

[0053] In some embodiments, the D100 particle size of the pulverized material is less than or equal to 10 μm.

[0054] In the above embodiments, the D100 particle size of the pulverized material is within the above range, which is beneficial for the removal of lithium ions after subsequent mixing with the aqueous solution of the second reducing agent, and for the subsequent slurrying to form a uniform and stable first slurry and second slurry, so as to obtain a high-purity, high-capacity composite sodium ferrous sulfate material through a second calcination treatment.

[0055] In some embodiments, the concentration of the second reducing agent in the aqueous solution is 0.1 mol / L to 0.2 mol / L.

[0056] In the above embodiments, the aqueous solution of the second reducing agent is used on the one hand to dissolve lithium ions in the pulverized material to separate lithium ions, and on the other hand to prevent ferrous ions from being oxidized in subsequent steps. The concentration of the second reducing agent is within the above range, which is beneficial to obtaining high-purity sodium ferrous sulfate precursor.

[0057] In some embodiments, the dispersion medium of the first slurry is selected from water, and the solid content of the first slurry is 30% to 40% by mass percentage.

[0058] In the above embodiments, the first slurry uses water as a medium and has a solid content between 30% and 40%, which is conducive to the uniform and stable dispersion of the sodium ferrous sulfate precursor in the first slurry. This is also conducive to the uniform mixing of the first slurry, carbon source, and third reducing agent in the subsequent process, so that a high-purity, high-capacity composite sodium ferrous sulfate material can be obtained through the second calcination treatment.

[0059] In some embodiments, the D50 particle size of the solid material in the second slurry is 100 nm to 300 nm.

[0060] In the above embodiments, the D50 particle size of the solid material in the second slurry is within the above range, which is conducive to the uniform and stable dispersion of the solid particles in the second slurry, and to the full contact between the carbon source, the third reducing agent and the sodium ferrous sulfate precursor, promoting the uniform formation of the carbon coating layer and reducing the oxidation of ferrous iron, thereby improving the electrochemical properties of the composite ferrous sulfate material, such as conductivity, cycle stability and capacity.

[0061] In some embodiments, the mass ratio of carbon source to iron in the second slurry is (0.35~1.2):1.

[0062] In the above embodiments, the mass ratio of carbon source to iron is within the above range, which is beneficial to forming a uniform and dense carbon coating layer, enhancing the electron transport performance of the composite ferrous sulfate material and its cycle stability during charge-discharge.

[0063] In some embodiments, the molar ratio of the third reducing agent to iron in the second slurry is (0.02 to 0.05):1.

[0064] In the above embodiments, the molar ratio of the third reducing agent to iron is within the above range, which is beneficial to reduce oxidation during the preparation process, especially the oxidation of ferrous ions in the second drying and second calcination processes, and is beneficial to obtaining high-purity and high-capacity composite ferrous sulfate materials.

[0065] In some embodiments, the D50 particle size of the second dried material is 4 μm to 10 μm.

[0066] In the above embodiments, the D50 particle size of the second dried material is within the above range, which helps to obtain a second calcined material with uniform particle size distribution and composition in the second calcination treatment, thereby improving the purity and electrochemical properties such as capacity of the prepared composite sodium ferrous sulfate material.

[0067] In some embodiments, the water content in the second dried material is less than 1.5% by weight.

[0068] In the above embodiments, controlling the moisture content of the second dried material to be below 1.5% is beneficial to reducing shrinkage and pore structure damage caused by moisture evaporation, improving the structural stability of the second calcined material, thereby improving the regularity and stability of the composite sodium ferrous sulfate material structure.

[0069] In some embodiments, the first reducing agent is selected from at least one of hydrazine hydrate, sodium borohydride, and sodium sulfite.

[0070] In the above embodiments, the first reducing agent is used to remove some iron ions (Fe). 3+ ) is reduced to ferrous ions (Fe) 2+The aforementioned reducing agent has high water solubility and reducing reactivity, which is beneficial for preparing high-purity composite sodium ferrous sulfate materials.

[0071] In some embodiments, the sodium salt is selected from at least one of sodium bicarbonate, sodium acetate, sodium citrate, sodium formate, and sodium benzoate.

[0072] In the above embodiments, the sodium salt has good water solubility, and while providing sodium ions, the anions are easy to remove, which helps to reduce the introduction of impurities into the composite sodium ferrous sulfate material and prepare high-purity composite sodium ferrous sulfate material.

[0073] In some embodiments, the second reducing agent is selected from at least one of hydrazine hydrate and sodium sulfite.

[0074] In the above embodiments, the second reducing agent reduces the oxidation of ferrous ions during the mixing and solid-liquid separation stages. Hydrazine hydrate and sodium sulfite have high water solubility and reducing reactivity. Using them as the second reducing agent to protect ferrous ions is beneficial for preparing high-purity composite sodium ferrous sulfate materials.

[0075] In some embodiments, the carbon source is selected from at least one of glucose, sucrose, PEG, and water-soluble starch.

[0076] In the above embodiments, the carbon source forms a carbon coating layer through high-temperature carbonization during the preparation of the composite sodium ferrous sulfate material, thereby enhancing the conductivity of the composite sodium ferrous sulfate material. Using glucose, sucrose, PEG, water-soluble starch, etc., as carbon sources is beneficial for forming a uniform carbon coating layer.

[0077] In some embodiments, the third reducing agent is selected from at least one of ascorbic acid and phosphorous acid.

[0078] In the above embodiments, the third reducing agent (ascorbic acid, phosphorous acid) reduces the oxidation of ferrous ions in the subsequent second drying and second calcination processes. Furthermore, the reducing agent still has a high reducing capacity at high temperatures. During the second calcination process, it reduces the oxidation of ferrous ions and promotes the formation of carbon layers, which helps to obtain a composite sodium ferrous sulfate material with stable structure and uniform composition.

[0079] In some embodiments, the oxygen content of the first protective atmosphere is less than 5 ppm.

[0080] In the above embodiments, the low oxygen content atmosphere helps to avoid oxidation under high temperature calcination conditions, improves the purity and structural stability of the prepared composite ferrous sulfate material, and thus improves the electrochemical properties such as capacity and cycle stability of the composite ferrous sulfate material.

[0081] In some embodiments, the heating rate for the first calcination is 200°C / h to 300°C / h.

[0082] In the above embodiments, the above heating rate is conducive to the uniform heating of the first dried material, forming a structurally stable first calcined material, thereby helping to obtain a structurally stable composite sodium ferrous sulfate material.

[0083] In some embodiments, the second protective atmosphere has a humidity of less than or equal to 5%, an oxygen content of less than 1 ppm, and a pressure of 20 Pa to 200 Pa.

[0084] In the above embodiments, the low humidity, low oxygen content atmosphere and low pressure conditions are conducive to reducing the oxidation and moisture adsorption of the second drying material under the high temperature calcination conditions of the second calcination treatment, improving the purity and structural stability of the composite ferrous sulfate material, thereby improving the capacity and cycle stability and other electrochemical properties of the composite ferrous sulfate material.

[0085] In some embodiments, the heating rate for the second calcination is from 40°C / h to 80°C / h.

[0086] In the above embodiments, the heating rate helps the carbon source carbonize to form a uniform carbon coating layer, thereby improving the electrical conductivity and structural stability of the composite sodium ferrous sulfate material.

[0087] Secondly, embodiments of this application provide a composite sodium ferrous sulfate material, comprising sodium ferrous sulfate and a carbon coating layer that at least partially coats the surface of the sodium ferrous sulfate; the general formula for sodium ferrous sulfate is Na. X Fe(SO4) Y C W The value of X ranges from 1.57 to 1.90, the value of Y ranges from 1.72 to 1.94, and the value of W ranges from 0 to 0.271; C is selected from at least one of borate, phosphate, silicate, and pyrophosphate; the mass fraction of carbon in the composite sodium ferrous sulfate material is 1.5% to 3%.

[0088] In the technical solution of this application embodiment, the carbon coating layer enhances the electronic conductivity of the composite sodium ferrous sulfate material, reduces internal resistance, and serves as a protective layer for the sodium ferrous sulfate, improving the cycle stability of the composite sodium ferrous sulfate material. By doping the sodium ferrous sulfate with ions such as borate, phosphate, silicate, or pyrophosphate, the crystal structure of the sodium ferrous sulfate is optimized, improving the sodium ion storage capacity and structural stability of the composite sodium ferrous sulfate material, thereby enhancing its cycle stability, conductivity, and electrochemical activity. Furthermore, the doped ions, especially silicate and phosphate, help regulate the active sites on the surface of the composite sodium ferrous sulfate material, reducing the water absorption tendency of sulfate, thus improving the stability of the composite sodium ferrous sulfate material in humid environments, reducing side reactions caused by water absorption inside the secondary battery, and extending the service life of the secondary battery. By using the carbon coating layer and controlling the ion doping content within the above range, it is beneficial to obtain a composite sodium ferrous sulfate material with high capacity, high coulombic efficiency, and good cycle stability.

[0089] In some embodiments, the D50 particle size range of the composite sodium ferrous sulfate material is 5 μm to 9 μm, and the D100 particle size range is 22 μm to 30 μm.

[0090] In the above embodiments, the particle size and distribution of the composite sodium ferrous sulfate material are within the above range, which is beneficial to optimize the electron and ion transport path of the composite sodium ferrous sulfate material, reduce the stress between the particles of the composite sodium ferrous sulfate material, improve the electrochemical activity and capacity of the composite sodium ferrous sulfate material, and improve the structural stability and cycle stability of the composite sodium ferrous sulfate material.

[0091] In some embodiments, the composite sodium ferrous sulfate material is spherical, and the sphericity of the composite sodium ferrous sulfate material is 0.82 to 0.95.

[0092] In the above embodiments, the spherical composite sodium ferrous sulfate material helps to reduce the voids between the composite sodium ferrous sulfate material particles, reduce stress concentration, improve the stability of the composite sodium ferrous sulfate material, and improve the cycle stability of the composite sodium ferrous sulfate material.

[0093] In some embodiments, the content of free sodium in the composite sodium ferrous sulfate material is less than 700 ppm.

[0094] In the above embodiments, the free sodium content is within the above range, which is beneficial to reduce the water absorption of the composite sodium ferrous sulfate material and improve the stability of the coating slurry during the preparation of the positive electrode sheet, thereby improving the electrochemical performance of the secondary battery, such as capacity and cycle stability.

[0095] In some embodiments, the specific surface area of ​​the composite sodium ferrous sulfate material is 7 m².2 / g to 14m 2 / g.

[0096] In the above embodiments, the specific surface area is within the above range, and the composite sodium ferrous sulfate material has a suitable number of active sites, which helps to improve the electrochemical performance of the composite sodium ferrous sulfate material, such as capacity, rate performance and coulombic efficiency.

[0097] In some embodiments, the powder resistivity of the composite sodium ferrous sulfate material is 48 Ω·cm to 99 Ω·cm.

[0098] In the above embodiments, the powder resistivity of the composite sodium ferrous sulfate material is within the above range. The composite sodium ferrous sulfate material has a uniformly coated carbon coating layer and uniformly distributed doped ions, which helps to reduce the electron transfer resistance and energy loss inside the secondary battery using the composite sodium ferrous sulfate material, and improve the electrochemical performance of the secondary battery such as charge and discharge efficiency, cycle stability and energy efficiency.

[0099] In some embodiments, the loose packing density of the composite sodium ferrous sulfate material is from 0.25 g / mL to 0.39 g / mL.

[0100] In the above embodiments, the density of the composite sodium ferrous sulfate material affects the energy density and conductivity of the secondary battery. Under the above loose packing density, the secondary battery has a higher energy density and charge / discharge efficiency. Furthermore, the composite sodium ferrous sulfate material has better flowability and processing performance, which facilitates the mass production of secondary batteries and improves the accuracy and efficiency of secondary battery assembly.

[0101] In some embodiments, the tap density of the composite sodium ferrous sulfate material is 0.7 g / mL to 0.87 g / mL.

[0102] In the above embodiments, at the above tap density, the secondary battery using composite sodium ferrous sulfate material has high energy density and charge / discharge efficiency.

[0103] In some embodiments, the compaction density of the composite sodium ferrous sulfate material is from 2.1 g / mL to 2.37 g / mL.

[0104] In the above embodiments, at the above compaction density, the secondary battery using composite sodium ferrous sulfate material has high energy density and charge / discharge efficiency.

[0105] Thirdly, embodiments of this application provide a positive electrode sheet, which includes a composite sodium ferrous sulfate material obtained by the above-mentioned lithium precipitation mother liquor recovery method or the above-mentioned composite sodium ferrous sulfate material.

[0106] In the above embodiments, the positive electrode sheet contains the aforementioned composite sodium ferrous sulfate material, thus possessing the advantages of high capacity, high coulombic efficiency, and good cycle stability.

[0107] Fourthly, embodiments of this application provide a secondary battery, including a positive electrode sheet, wherein the positive electrode sheet is the aforementioned positive electrode sheet.

[0108] In the above embodiments, the secondary battery includes the aforementioned positive electrode sheet, thus possessing the advantages of high capacity, high coulombic efficiency, and good cycle stability.

[0109] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description

[0110] To more clearly illustrate the technical solution of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.

[0111] Figure 1 This is a flowchart of a lithium precipitation mother liquor recovery method based on an embodiment of the present invention;

[0112] Figure 2 Here is a SEM image of the first calcined material in Example 1;

[0113] Figure 3 The image shows the XRD pattern of the first calcined material in Example 1.

[0114] Figure 4 SEM image of the composite sodium ferrous sulfate material prepared in Example 1;

[0115] Figure 5 The graphs show the charge-discharge results of the composite sodium ferrous sulfate materials in Examples 1-5. Detailed Implementation

[0116] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.

[0117] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.

[0118] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.

[0119] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0120] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0121] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).

[0122] In the description of the embodiments of this application, unless otherwise specified, "ppm" means the mass of the tested element, molecule or ion in parts per million of the sample mass.

[0123] In the description of the embodiments of this application, unless otherwise specified, "content" refers to the mass percentage of the tested element, molecule or ion in the sample.

[0124] In the description of the embodiments of this application, unless otherwise specified, the solvents in "water", "washing water", "mother liquor", "solution" and "slurry" are each independently selected from at least one of distilled water, deionized water, pure water and ultrapure water.

[0125] As described in the background section, existing technologies face the challenge of effectively separating sodium and lithium when processing lithium precipitation mother liquor. To address this issue, this application provides a method for recovering lithium precipitation mother liquor, a composite sodium ferrous sulfate material, a positive electrode, and a secondary battery. This method achieves effective separation of lithium and sodium ions from the lithium precipitation mother liquor, with high recovery rates of elements such as sodium, iron, and sulfur. Furthermore, it facilitates the production of high-purity and high-capacity composite sodium ferrous sulfate material, thereby improving the performance of the positive electrode and the secondary battery.

[0126] Firstly, such as Figure 1 As shown in the figure, this application provides a method for recovering lithium precipitation mother liquor, including the following steps:

[0127] Adjust the pH of the lithium precipitation mother liquor to less than or equal to 5 to obtain the first mother liquor;

[0128] The first mother liquor is mixed with ferrous sulfate, sodium salt and the first reducing agent to obtain the first mixture;

[0129] The first mixture undergoes a first drying process to obtain a first dried material;

[0130] The first dried material undergoes a first calcination process to obtain the first calcined material;

[0131] The first calcined material was pulverized to obtain pulverized material;

[0132] After the pulverized material is mixed with an aqueous solution of the second reducing agent, it is subjected to solid-liquid separation to obtain sodium ferrous sulfate precursor.

[0133] The sodium ferrous sulfate precursor was subjected to pulping treatment to obtain the first pulp;

[0134] The first slurry, carbon source, and third reducing agent are mixed and then ground to obtain the second slurry;

[0135] The second slurry undergoes a second drying process to obtain the second dried material;

[0136] The second dried material was subjected to a second calcination treatment to obtain a composite sodium ferrous sulfate material;

[0137] The molar ratio of sodium, iron, and sulfate in the first mixture is (2.05–2.10):1 (2.02–2.10). Specifically, but not limitingly, the molar ratio of sodium, iron, and sulfate in the first mixture is 2.08:1:2.06, 2.05:1:2.02, 2.10:1:2.10, or any value within the range of any two of the above ratios.

[0138] In the technical solution of this application embodiment, the pH value of the lithium precipitation mother liquor is adjusted to be less than or equal to 5. Using sulfate and sodium ions in the lithium precipitation mother liquor as sulfate and sodium ion sources, ferrous sulfate is first added to the lithium precipitation mother liquor as an iron source, followed by drying and calcination to obtain a first calcined material containing sodium ferrous sulfate precursor. The sodium ferrous sulfate precursor generated after calcination is poorly soluble in water. Furthermore, during the aforementioned drying and calcination process, lithium ions do not participate in the reaction and therefore exist in the sodium ferrous sulfate precursor in the form of lithium ions, which are easily washed out by water. By pulverizing the first calcined material, the pulverized material is mixed with an aqueous solution of a second reducing agent, and solid-liquid separation is performed to effectively separate lithium ions, obtaining a high-purity sodium ferrous sulfate precursor. Then, the sodium ferrous sulfate precursor is subjected to slurry treatment, supplemented with carbon source and third reducing agent, and then ground, dried and calcined. The carbon source is carbonized at high temperature and the sodium ferrous sulfate is coated with carbon in situ. The third reducing agent avoids the oxidation of ferrous ions during the grinding and drying process, which is conducive to obtaining high-purity and high-capacity composite sodium ferrous sulfate material. The process is simple and the recovery rate of elements such as sodium, iron and sulfur is high.

[0139] Further, in some embodiments, the concentration of sodium in the first mother liquor is 45 g / L to 47 g / L, specifically, but not limitingly, the concentration of sodium is 45 g / L, 45.5 g / L, 46 g / L, 46.4 g / L, 46.9 g / L, 47 g / L, or any value within the range of any two of the above values; the concentration of sulfate is 185 g / L to 200 g / L, specifically, but not limitingly, the concentration of sulfate is 185 g / L, 187.5 g / L, 190 g / L, 195 g / L, 197.5 g / L, 200 g / L, or any value within the range of any two of the above values; the concentration of lithium is 1.6 g / L to 1.7 g / L, specifically, but not limitingly, the concentration of lithium is 1.6 g / L. The concentration of iron is 0.1 mg / L to 0.3 mg / L, specifically but not limitingly, the concentration of iron is 0.1 mg / L, 0.12 mg / L, 0.15 mg / L, 0.2 mg / L, 0.25 mg / L, 0.3 mg / L, or any value within the range of any two of the above values; the concentration of calcium is 21 mg / L to 23 mg / L, specifically but not limitingly, the concentration of calcium is 21 mg / L, 21.5 mg / L, 22 mg / L, 22.8 mg / L, 23 mg / L, or any value within the range of any two of the above values.

[0140] In the technical solution of this application embodiment, the recovery treatment of the first mother liquor helps to fully recover sulfate, lithium, and sodium elements, and the recovered composite sodium ferrous sulfate material has good comprehensive performance.

[0141] Furthermore, in some embodiments, the first mixture further includes a dopant selected from at least one of boric acid, phosphoric acid, silicic acid, and pyrophosphate. The molar ratio of the dopant to sodium in the first mixture is (0.05 to 0.1):1. Specifically, but not limitingly, the molar ratio of the dopant to sodium in the first mixture is 0.05:1, 0.08:1, 0.1:1, or any value within the range of any two of the above ratios.

[0142] In the technical solution of this application embodiment, the introduction of the above-mentioned dopants such as phosphoric acid and pyrophosphoric acid improves the conductivity and electrochemical activity of the prepared composite ferrous sulfate material. By adding the above-mentioned dopants (boric acid, phosphoric acid, silicic acid, pyrophosphoric acid, etc.) and precisely controlling their molar ratio with sodium, it is beneficial to improve the electrochemical performance of the composite sodium ferrous sulfate material as a positive electrode material, such as capacity, cycle stability and coulombic efficiency.

[0143] Furthermore, in some embodiments, the step of adjusting the pH of the lithium precipitation mother liquor to less than or equal to 5 includes:

[0144] Add sulfuric acid solution to the lithium precipitation mother liquor until the pH value of the lithium precipitation mother liquor is 2 to 5.

[0145] Under the aforementioned pH conditions, it is beneficial to form a structurally stable sodium ferrous sulfate precursor, thereby improving the recovery rates of elements such as sodium, iron, and sulfur, as well as the separation effect between sodium and lithium. Furthermore, using a sulfuric acid solution to adjust the pH value provides a partial source of sulfuric acid and reduces the introduction of impurities, which is conducive to obtaining high-purity composite sodium ferrous sulfate materials. Specifically, the sulfuric acid solution can be selected from commercially available concentrated sulfuric acid or an aqueous solution of sulfuric acid obtained by diluting concentrated sulfuric acid.

[0146] Furthermore, in some embodiments, the step of subjecting the first dried material to a first calcination treatment to obtain the first calcined material includes:

[0147] The first dried material is subjected to a first protective atmosphere and a first calcination temperature, and then subjected to a first calcination time to obtain a first calcined material; wherein the first protective atmosphere is selected from one or more of nitrogen atmosphere, carbon dioxide atmosphere, and argon atmosphere, the first calcination temperature is 300℃ to 400℃, and the first calcination time is 10h to 20h. Specifically, but not limitingly, the first calcination temperature is 300℃, 350℃, 400℃, or any value within the range of any two of the above values, and the first calcination time is 10h, 15h, 20h, or any value within the range of any two of the above values.

[0148] Furthermore, in some embodiments, the mass fraction of sodium in the first calcined feedstock is 16% to 17%, specifically, but not limitingly, the mass fraction of sodium is 16%, 16.42%, 16.54%, 16.96%, 17%, or any value within the range of any two of the above values; the mass fraction of iron is 19% to 21%, specifically, but not limitingly, the mass fraction of iron is 19%, 19.46%, 19.7%, 20%, 20.18%, 21%, or any value within the range of any two of the above values; and the mass fraction of sulfur is 22% to 24%. Specifically, but not limited to, the mass fraction of sulfur is 22%, 22.5%, 22.76%, 22.97%, 23%, 23.43%, 24%, or any value within the range of any two of the above values; the mass fraction of lithium is 0.5% to 0.6%, specifically, but not limited to, the mass fraction of lithium is 0.5%, 0.52%, 0.53%, 0.55%, 0.58%, 0.59%, 0.6%, or any value within the range of any two of the above values; the mass fraction of trivalent iron (III) is 0.03% to 0.12%, specifically, but not limited to... Specifically, the mass fraction of ferric iron (III) is 0.03%, 0.05%, 0.08%, 0.12%, or any value within the range of any two of the above values; the mass fraction of carbon is 0.09% to 0.13%, specifically but not specifically, the mass fraction of carbon is 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, or any value within the range of any two of the above values; the molar ratio of sodium to iron is 1.9 to 2.2, specifically but not specifically, the molar ratio of sodium to iron is 1.9 or 1.9. 8, 2.04, 2.12, 2.2, or any value within the range of any two of the above values; the aluminum content is 1.2ppm to 1.8ppm, specifically, but not limitingly, the aluminum content is 1.2ppm, 1.5ppm, 1.8ppm, or any value within the range of any two of the above values; the calcium content is 28ppm to 32ppm, specifically, but not limitingly, the calcium content is 28ppm, 28.11ppm, 29.56ppm, 31.67ppm, 32ppm, or any value within the range of any two of the above values. The pH value of the first calcined material is 4 to 5.3, specifically, but not limitingly, the pH value of the first calcined material is 4, 4.05, 4.28, 4.5, 5, 5.1, 5.29, or any value within the range of any two of the above values.

[0149] In the technical solution of this application embodiment, high-temperature calcination under protective gas effectively prevents the oxidation of ferrous ions, which is beneficial to improving the structural stability and purity of the obtained composite sodium ferrous sulfate material. Furthermore, the aforementioned first calcination temperature and first calcination time contribute to the uniform and complete crystallization of the composite sodium ferrous sulfate material, facilitating subsequent thorough washing and removal of lithium ions, high-yield recovery of elements such as sodium, iron, and sulfur, and obtaining a composite sodium ferrous sulfate material with excellent electrochemical performance.

[0150] Furthermore, in some embodiments, the step of mixing the pulverized material with an aqueous solution of the second reducing agent, followed by solid-liquid separation to obtain the sodium ferrous sulfate precursor, includes:

[0151] The pulverized material is mixed with an aqueous solution of a second reducing agent, and after a first mixing temperature and a first mixing time, a second mixture is obtained.

[0152] The second mixture was separated into solid and liquid components to obtain solid material. The solid material was washed until the conductivity of the wash water was less than or equal to 300 μS / cm to obtain sodium ferrous sulfate precursor.

[0153] The first mixing time is 1 to 3 hours, and the first mixing temperature is 40°C to 80°C. Specifically, but not limitingly, the first mixing time is any value within the range of 1 hour, 2 hours, 3 hours, or any two of the above values; the first mixing temperature is any value within the range of 40°C, 60°C, 80°C, or any two of the above values.

[0154] In the technical solution of this application embodiment, the pulverized material and the aqueous solution of the second reducing agent are mixed at a first mixing temperature (40°C to 80°C) for a first mixing time (1h to 3h), which is beneficial to fully dissolve impurity ions such as lithium ions in the pulverized material to obtain a second mixture. After solid-liquid separation and further washing, the second mixture is beneficial to obtain a high-purity sodium ferrous sulfate precursor.

[0155] Furthermore, in some embodiments, the step of subjecting the second dried material to a second calcination treatment to obtain the composite sodium ferrous sulfate material includes:

[0156] The second dried material is subjected to a second protective atmosphere and a second calcination temperature, followed by a second calcination time, to obtain a composite sodium ferrous sulfate material. The second protective atmosphere is selected from one or more of nitrogen, carbon dioxide, and argon atmospheres; the second calcination temperature is 300℃ to 350℃; and the second calcination time is 6 h to 12 h. Specifically, but not limitingly, the second calcination temperature is 300℃, 320℃, 350℃, or any value within the range of any two of the above values; and the second calcination time is 6 h, 8 h, 10 h, 12 h, or any value within the range of any two of the above values.

[0157] In the technical solution of this application embodiment, the second calcination treatment under a second protective atmosphere facilitates the full reaction of the various components (such as sodium ferrous sulfate, carbon source, and dopant) in the second dried material at high temperature, which helps to improve the crystal structure of the sodium ferrous sulfate material and promotes the full doping of the dopant elements in the dopant, thereby improving the electrochemical performance of the composite sodium ferrous sulfate material. Furthermore, after calcination at the aforementioned second calcination temperature (300°C to 350°C) for a second calcination time (6h to 12h), the carbon source is fully carbonized at high temperature, forming a carbon coating layer, which effectively enhances the electronic conductivity of the composite sodium ferrous sulfate material and reduces its internal resistance. Through the aforementioned second calcination treatment, the prepared composite sodium ferrous sulfate material exhibits good electronic and ionic conductivity, which is beneficial for improving the coulombic efficiency, capacity, and other electrochemical properties of the composite sodium ferrous sulfate material.

[0158] Furthermore, in some embodiments, the lithium precipitation mother liquor recovery method further includes:

[0159] The first filtrate obtained after solid-liquid separation of the second mixture is mixed with the washing water after washing the solid material to obtain a lithium-containing washing solution. The pH value of the lithium-containing washing solution is adjusted to 9 to 10.5 to obtain a lithium-containing solution. The lithium-containing solution is mixed with sodium phosphate to obtain a third mixture. The third mixture is then subjected to solid-liquid separation to obtain lithium phosphate.

[0160] In the aforementioned lithium-containing detergent solution, the concentration of sodium is 4.2 g / mL to 4.7 g / mL, specifically, but not limitingly, the concentration of sodium is 4.2 g / mL, 4.24 g / mL, 4.35 g / mL, 4.69 g / mL, 4.7 g / mL, or any value within the range of any two of the above values; the concentration of sulfate is 16.5 g / mL to 20 g / mL, specifically, but not limitingly, the concentration of sulfate is 16.5 g / mL, 16.52 g / mL, 17 g / mL, 19.6 g / mL, 19.9 g / mL, or 10.9 g / mL. The lithium concentration is 2.14 g / L to 2.18 g / L, specifically, but not limitingly, 2.14 g / L, 2.16 g / L, 2.18 g / L, or any value within the range of any two of the above values; the iron concentration is 0.2 mg / L to 0.9 mg / L, specifically, but not limitingly, 0.2 mg / L, 0.5 mg / L, 0.9 mg / L, or any value within the range of any two of the above values. The pH value of the lithium-containing detergent solution is 8.5 to 9.1, specifically, but not limitingly, 8.5, 8.54, 8.72, 9.02, 9.1, or any value within the range of any two of the above values.

[0161] In the aforementioned lithium phosphate, the mass fraction of lithium is 17% to 18%, specifically, but not limitingly, the mass fraction of lithium is 17%, 17.47%, 17.53%, 17.54%, 18%, or any value within the range of any two of the above values; the mass fraction of phosphorus is 26% to 27%, specifically, but not limitingly, the mass fraction of phosphorus is 26%, 26.2%, 26.4%, 26.71%, 26.79%, 26.86%, 27%, or any value within the range of any two of the above values; the content of iron is 3.6 ppm to 10.3 ppm, specifically, but not limitingly, the iron content is 3.6 ppm, 8.7 ppm, 10.3 ppm, or... The sodium content is 114 ppm to 137 ppm, specifically, but not limited to, 114 ppm, 135 ppm, 137 ppm, or any value within the range of any two of the above values; the calcium content is 19 ppm to 25 ppm, specifically, but not limited to, 19.6 ppm, 20.4 ppm, 24.8 ppm, or any value within the range of any two of the above values; the water content is 345 ppm to 570 ppm, specifically, but not limited to, 345 ppm, 367 ppm, 567 ppm, or any value within the range of any two of the above values. The BET specific surface area of ​​lithium phosphate is 9.3 m². 2 / g~19.5m 2 / g, specifically, but not limitingly, the BET specific surface area of ​​lithium phosphate is 9.3m². 2 / g, 10m 2 / g, 19.5m 2 / g or any value within the range of any two of the above values. The D50 particle size of lithium phosphate is 3.5μm to 6.5μm, specifically, but not limitingly, 3.6μm, 5.7μm, 6.4μm or any value within the range of any two of the above values. The magnetic material content of lithium phosphate is 0.21ppm to 0.27ppm, specifically, but not limitingly, 0.21ppm, 0.24ppm, 0.27ppm or any value within the range of any two of the above values.

[0162] In the technical solution of this application embodiment, the first filtrate and the washing water contain a high concentration of lithium ions. After mixing the two, they are mixed with sodium phosphate to obtain lithium phosphate, thus achieving the separation and recovery of lithium ions in the lithium precipitation mother liquor. The small amount of sodium ions, sulfate ions, and lithium ions remaining in the filtrate obtained after the solid-liquid separation of the third mixture can be returned to the lithium precipitation mother liquor for recycling.

[0163] Furthermore, in some embodiments, the molar ratio of sodium phosphate to lithium in the lithium-containing solution is 1:(2.7 to 2.9), which is conducive to the full precipitation of lithium; specifically, but not limitingly, the molar ratio of sodium phosphate to lithium in the lithium-containing solution is 1:2.7, 1:2.8, 1:2.9 or any value within the range of any two of the above ratios.

[0164] Further, in some embodiments, the lithium-containing solution is mixed with sodium phosphate to obtain a third mixture, and the third mixture is subjected to solid-liquid separation to obtain lithium phosphate, including:

[0165] Sodium phosphate was added to a lithium-containing solution at 60°C to 90°C and stirred for 1 to 2 hours to obtain a third mixture. The filter residue obtained by solid-liquid separation of the third mixture was washed and dried to obtain lithium phosphate.

[0166] In the technical solution of this application embodiment, under the above-mentioned temperature and time conditions, it is beneficial to obtain lithium phosphate with high yield and high purity, thereby achieving efficient and full recovery of lithium element.

[0167] Furthermore, in some embodiments, the second calcination treatment further includes:

[0168] The calcined material obtained by calcining the second dried material under a second protective atmosphere and a second calcination temperature for a second calcination time is cooled to a temperature less than or equal to 100°C to obtain a cooled material.

[0169] The cooled material is sequentially screened and iron removed to obtain a composite sodium ferrous sulfate material.

[0170] In the technical solution of this application embodiment, by finely controlling the cooling, sieving and iron removal of the calcined material, it is helpful to improve the purity, size consistency and electrochemical performance of the composite sodium ferrous sulfate material, which is beneficial to the preparation of high-performance secondary batteries.

[0171] Furthermore, in some embodiments, the molar ratio of the first reducing agent to the iron element in the first mixture is (0.05 to 0.1):1; specifically, but not limitingly, the molar ratio of the first reducing agent to the iron element in the first mixture is 0.05:1, 0.06:1, 0.08:1, 0.1:1, or any value within the range of any two of the above ratios.

[0172] In the technical solution of this application embodiment, the molar ratio of the first reducing agent to the iron element in the first mixture is within the above range, which helps to reduce the oxidation of ferrous ions in the subsequent mixing, drying and calcination process, improve the purity and structural stability of the sodium ferrous sulfate precursor obtained from the first calcined material, facilitate the reduction of iron element mixing during the washing and removal of lithium ions, and improve the purity of the prepared composite sodium ferrous sulfate material.

[0173] Furthermore, in some embodiments, the first drying process and the second drying process are each independently performed using spray drying.

[0174] In the technical solution of this application embodiment, spray drying helps to control the particle size of the first dried material and the second dried material, and obtain the first dried material and the second dried material with a high degree of uniform particle size, which is beneficial to improving the electrochemical activity and ion transport capability of the composite sodium ferrous sulfate material; in addition, as an efficient and rapid drying method, spray drying is beneficial to significantly shorten the drying time, reduce energy consumption, improve production efficiency, and is suitable for continuous large-scale production.

[0175] Furthermore, in some embodiments, the D50 particle size of the first dried material is 5 μm to 15 μm, specifically, but not limitingly, the D50 particle size of the first dried material is 5 μm, 6 μm, 7 μm, 8 μm, 10 μm, 12 μm, 15 μm or any value within the range of any two of the above values.

[0176] In the technical solution of this application embodiment, the D50 particle size of the first dried material is within the above-mentioned range, which helps to obtain a first calcined material with concentrated particle size and uniform composition by utilizing the first calcination treatment, thereby improving the purity of the obtained sodium ferrous sulfate precursor.

[0177] Furthermore, in some embodiments, the water content in the first dried material is less than 1.5% by mass percentage.

[0178] In the technical solution of this application embodiment, the first drying treatment removes moisture from the first mixture, reducing the impact of moisture evaporation during the high-temperature calcination process in the subsequent first calcination treatment on the material structure of the first calcined material. Controlling the moisture content of the first dried material to below 1.5% helps reduce the shrinkage and pore structure damage of the first calcined material caused by moisture evaporation, improves the structural stability of the first calcined material, and thus improves the regularity and stability of the structure of the subsequently prepared composite sodium ferrous sulfate material.

[0179] Furthermore, in some embodiments, the D100 particle size of the pulverized material is less than or equal to 10 μm.

[0180] In the technical solution of this application embodiment, the D100 particle size of the pulverized material is within the above-mentioned range, which is beneficial for the removal of lithium ions after subsequent mixing with the aqueous solution of the second reducing agent, and for the subsequent slurry formation of a uniform and stable first slurry and second slurry, so as to obtain a high-purity, high-capacity composite sodium ferrous sulfate material through a second calcination treatment.

[0181] In some embodiments, the D100 particle size of the pulverized material is greater than or equal to 2 μm and less than or equal to 10 μm, for example, it can be 2 μm, 3 μm, 5 μm, 6 μm, 8 μm, 10 μm, etc.

[0182] Furthermore, in some embodiments, the concentration of the second reducing agent in the aqueous solution is from 0.1 mol / L to 0.2 mol / L. Specifically, but not limitingly, the concentration of the second reducing agent in the aqueous solution is 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, or any value within the range of any two of the above values.

[0183] In the technical solution of this application embodiment, the aqueous solution of the second reducing agent is used on the one hand to dissolve lithium ions in the pulverized material to separate lithium ions, and on the other hand to prevent ferrous ions from being oxidized in subsequent steps. The concentration of the second reducing agent is within the above range, which is beneficial to obtaining high-purity sodium ferrous sulfate precursor.

[0184] Furthermore, in some embodiments, the dispersion medium in the first slurry is selected from water, and the solid content of the first slurry is 30% to 40% by mass percentage. Specifically, but not limitingly, the solid content of the first slurry is 30%, 32%, 34%, 35%, 36%, 38%, 40%, or any value within the range of any two of the above values.

[0185] In the technical solution of this application embodiment, the first slurry uses water as a medium and has a solid content between 30% and 40%, which is conducive to the uniform and stable dispersion of sodium ferrous sulfate precursor in the first slurry, and is conducive to the uniform mixing of the first slurry, carbon source and third reducing agent in the subsequent process, so as to obtain high-purity and high-capacity composite sodium ferrous sulfate material in the second calcination treatment.

[0186] Furthermore, in some embodiments, the D50 particle size of the solid material in the second slurry is from 100 nm to 300 nm; specifically, but not limitingly, the D50 particle size of the solid material in the second slurry is 100 nm, 120 nm, 150 nm, 200 nm, 250 nm, 300 nm or any value within the range of any two of the above values.

[0187] In the technical solution of this application embodiment, the D50 particle size of the solid material in the second slurry is within the above range, which is conducive to the uniform and stable dispersion of the solid particles in the second slurry, and to the full contact between the carbon source, the third reducing agent and the sodium ferrous sulfate precursor, promoting the uniform formation of the carbon coating layer and reducing the oxidation of ferrous iron, thereby improving the electrochemical properties of the composite ferrous sulfate material, such as conductivity, cycle stability and capacity.

[0188] Furthermore, in some embodiments, the mass ratio of carbon source to iron in the second slurry is (0.35~1.2):1. Specifically, but not limitingly, the mass ratio of carbon source to iron in the second slurry is 0.35:1, 0.38:1, 0.4:1, 0.5:1, 0.7:1, 0.9:1, 1.0:1, 1.2:1, or any value within the range of any two of the above ratios.

[0189] In the technical solution of this application embodiment, the mass ratio of carbon source to iron element is within the above range, which is beneficial to forming a uniform and dense carbon coating layer, enhancing the electron transport performance of the composite ferrous sulfate material and its cycle stability during charge-discharge process.

[0190] Furthermore, in some embodiments, the molar ratio of the third reducing agent to iron in the second slurry is (0.02 to 0.05):1; specifically, but not limitingly, the molar ratio of the third reducing agent to iron in the second slurry is 0.02:1, 0.03:1, 0.04:1, 0.05:1, or any value within the range of any two of the above ratios.

[0191] In the technical solution of this application embodiment, the molar ratio of the third reducing agent to iron element is within the above range, which is beneficial to reduce oxidation during the preparation process, especially the oxidation of ferrous ions in the second drying treatment and the second calcination treatment, and is beneficial to obtaining high-purity and high-capacity composite ferrous sulfate material.

[0192] Furthermore, in some embodiments, the D50 particle size of the second dried material is 4 μm to 10 μm; specifically, but not limitingly, the D50 particle size of the second dried material is 4 μm, 6 μm, 8 μm, 10 μm or any value within the range of any two of the above values.

[0193] In the technical solution of this application embodiment, the D50 particle size of the second dried material is within the above range, which helps to obtain a second calcined material with uniform particle size distribution and uniform composition in the second calcination treatment, thereby improving the purity and electrochemical properties such as capacity of the prepared composite sodium ferrous sulfate material.

[0194] Furthermore, in some embodiments, the water content in the second dried material is less than 1.5% by mass percentage.

[0195] In the technical solution of this application embodiment, controlling the moisture content of the second dried material to be below 1.5% is beneficial to reduce shrinkage and pore structure damage caused by moisture evaporation, improve the structural stability of the second calcined material, and thus improve the regularity and stability of the composite sodium ferrous sulfate material structure.

[0196] Furthermore, in some embodiments, the first reducing agent is selected from at least one of hydrazine hydrate, sodium borohydride, and sodium sulfite.

[0197] In the technical solution of this application embodiment, the first reducing agent is used to remove some iron ions (Fe 3+ ) is reduced to ferrous ions (Fe) 2+ The aforementioned reducing agent has high water solubility and reducing reactivity, which is beneficial for preparing high-purity composite sodium ferrous sulfate materials.

[0198] Furthermore, in some embodiments, the sodium salt is selected from at least one of sodium bicarbonate, sodium acetate, sodium citrate, sodium formate, and sodium benzoate.

[0199] In the technical solution of this application embodiment, the above-mentioned sodium salt has good water solubility, and while providing sodium ions, the anions are easy to remove, which is beneficial to reduce the introduction of impurities into the composite sodium ferrous sulfate material and prepare high-purity composite sodium ferrous sulfate material.

[0200] Furthermore, in some embodiments, the second reducing agent is selected from at least one of hydrazine hydrate and sodium sulfite.

[0201] In the technical solution of this application embodiment, the second reducing agent reduces the oxidation of ferrous ions during the mixing and solid-liquid separation stages. Hydrazine hydrate and sodium sulfite have high water solubility and reduction reactivity. Using them as the second reducing agent protects the ferrous ions, which is beneficial for preparing high-purity composite sodium ferrous sulfate materials.

[0202] Furthermore, in some embodiments, the carbon source is selected from at least one of glucose, sucrose, PEG, and water-soluble starch.

[0203] In the technical solution of this application embodiment, the carbon source forms a carbon coating layer through high-temperature carbonization during the preparation of the composite sodium ferrous sulfate material, thereby enhancing the conductivity of the composite sodium ferrous sulfate material. Using glucose, sucrose, PEG, water-soluble starch, etc., as carbon sources is beneficial for forming a uniform carbon coating layer.

[0204] Furthermore, in some embodiments, the third reducing agent is selected from at least one of ascorbic acid and phosphorous acid.

[0205] In the technical solution of this application embodiment, the third reducing agent (ascorbic acid, phosphorous acid) reduces the oxidation of ferrous ions in the subsequent second drying treatment and second calcination treatment. Furthermore, the reducing agent still has a high reducing ability at high temperature. In the second calcination treatment, it reduces the oxidation of ferrous ions and promotes the formation of carbon layers, which helps to obtain a composite sodium ferrous sulfate material with stable structure and uniform composition.

[0206] Furthermore, in some embodiments, the oxygen content of the first protective atmosphere is less than 5 ppm.

[0207] In the technical solution of this application embodiment, under the above-mentioned low oxygen content atmosphere, it is beneficial to avoid oxidation under high temperature calcination conditions, improve the purity and structural stability of the prepared composite ferrous sulfate material, thereby improving the electrochemical performance of the composite ferrous sulfate material such as capacity and cycle stability.

[0208] Furthermore, in some embodiments, the furnace pressure of the first calcination is 20 Pa to 300 Pa, and the humidity is 0.1% to 1.5%; specifically, but not limitingly, the furnace pressure of the first calcination is 20 Pa, 150 Pa, 300 Pa, or any value within the range of any two of the above values, and the humidity is 0.1%, 8%, 1.5%, or any value within the range of any two of the above values.

[0209] In the technical solution of this application embodiment, under the above-mentioned furnace pressure and humidity conditions, the integrity of the calcined product is higher and its structural stability is higher, which is beneficial to improving the cycle stability of the composite ferrous sulfate material.

[0210] Furthermore, in some embodiments, the heating rate for the first calcination is 200°C / h to 300°C / h.

[0211] In the technical solution of this application embodiment, at the above heating rate, it is beneficial for the first dry material to be heated evenly, forming a structurally stable first calcined material, thereby helping to obtain a structurally stable composite sodium ferrous sulfate material.

[0212] Furthermore, in some embodiments, the second protective atmosphere has a humidity of less than or equal to 5%, an oxygen content of less than 1 ppm, and a pressure of 20 Pa to 100 Pa.

[0213] In the technical solution of this application embodiment, the low humidity, low oxygen content atmosphere and low pressure conditions are conducive to reducing the oxidation and moisture adsorption of the second drying material under the high temperature calcination conditions of the second calcination treatment, improving the purity and structural stability of the composite ferrous sulfate material, thereby improving the capacity and cycle stability and other electrochemical properties of the composite ferrous sulfate material.

[0214] Furthermore, in some embodiments, the heating rate for the second calcination is 40°C / h to 80°C / h.

[0215] In the technical solution of this application embodiment, the above-mentioned heating rate helps the carbon source to carbonize and form a uniform carbon coating layer, thereby improving the electrical conductivity and structural stability of the composite sodium ferrous sulfate material.

[0216] In some embodiments, the sodium recovery rate of the above-described lithium precipitation mother liquor recovery method is 94% to 95%, for example, it can be 94.1%, 94.2%, 94.5%, 94.6%, 94.7%, 94.9%, 95%, etc.

[0217] In some embodiments, the sulfur recovery rate of the above-described lithium precipitation mother liquor recovery method is 94.5% to 96.5%, for example, it can be 94.5%, 94.8%, 95%, 95.6%, 95.9%, 96%, 96.2%, 96.5%, etc.

[0218] In some embodiments, the lithium recovery rate of the above-described lithium precipitation mother liquor recovery method is 96.5% to 97.7%, for example, it can be 96.5%, 96.8%, 97%, 97.2%, 97.5%, 97.7%, etc.

[0219] Lithium-ion batteries, with their high energy density, long cycle life, and environmental friendliness, have become an indispensable energy source for portable electronic devices, electric vehicles, and large-scale energy storage systems. Sodium and lithium belong to the same group in the periodic table and have similar physical and chemical properties. Compared to lithium resources, sodium is abundant in the Earth's crust, evenly distributed, and inexpensive. Therefore, sodium-ion batteries are the most promising candidates for large-scale power storage and low-speed transportation. Sodium ferrous sulfate is a positive electrode material for iron-based sulfate polyanionic sodium-ion batteries, possessing advantages such as high operating voltage, abundant raw materials, low cost, and environmental friendliness. However, some problems remain to be solved, such as poor electronic conductivity and the easy oxidation of ferrous ions, which affect the battery's capacity, efficiency, and stability. Therefore, developing new sodium ferrous sulfate materials to improve the capacity, efficiency, and stability of materials is of great significance.

[0220] To address the aforementioned problems, in a second aspect, embodiments of this application provide a composite sodium ferrous sulfate material, comprising sodium ferrous sulfate and a carbon coating layer at least partially covering the surface of the sodium ferrous sulfate; the general formula for sodium ferrous sulfate is Na. X Fe(SO4) Y C W The value of X ranges from 1.57 to 1.90, preferably from 1.79 to 1.90; the value of Y ranges from 1.72 to 1.94; and the value of W ranges from 0 to 0.271, preferably from 0.054 to 0.135.

[0221] Specifically, but not limitingly, the chemical formula of sodium ferrous sulfate is Na. 1.87 Fe(SO4) 1.79 (BO3) 0.108 Na 1.88 Fe(SO4) 1.86 (BO3) 0.108Na 1.84 Fe(SO4) 1.72 (BO3) 0.108 Na 1.87 Fe(SO4) 1.79 (BO3) 0.108 Na 1.79 Fe(SO4) 1.82 (PO4) 0.062 Na 1.82 Fe(SO4) 1.94 (SiO4) 0.131 Na 1.90 Fe(SO4) 1.82 (BO3) 0.111 Na 1.87 Fe(SO4) 1.79 (BO3) 0.135 Na 1.87 Fe(SO4) 1.79 (SiO4) 0.108 Na 1.87 Fe(SO4) 1.79 (P2O7) 0.054 Na 1.85 Fe(SO4) 1.73 (BO3) 0.106 Na 1.86 Fe(SO4) 1.81 (BO3) 0.109 At least one of the following. C is selected from at least one of borate, phosphate, silicate, and pyrophosphate; the mass fraction of carbon in the composite sodium ferrous sulfate material is 1.5% to 3%.

[0222] In the technical solution of this application embodiment, the carbon coating layer significantly enhances the electronic conductivity of the composite sodium ferrous sulfate material, reduces internal resistance, and serves as a protective layer for the sodium ferrous sulfate, improving the cycle stability of the composite sodium ferrous sulfate material. By doping the sodium ferrous sulfate with ions such as borate, phosphate, silicate, or pyrophosphate, the crystal structure of the sodium ferrous sulfate is optimized, improving the sodium ion storage capacity and structural stability of the composite sodium ferrous sulfate material. In addition, these doped ions can act as a structural "scaffold," preventing structural collapse during sodium ion insertion and extraction, thus improving the cycle stability of the composite sodium ferrous sulfate material. Phosphoric acid and pyrophosphate may improve the conductivity and electrochemical activity of the composite sodium ferrous sulfate material by forming phosphorus-iron bonds or phosphorus-sodium bonds. Furthermore, the doped ions, especially silicate and phosphate, are beneficial for regulating the active sites on the surface of the composite sodium ferrous sulfate material, reducing the water absorption tendency of sulfate, thereby improving the stability of the composite sodium ferrous sulfate material in humid environments, reducing side reactions caused by water absorption inside the secondary battery, and extending the service life of the secondary battery. By using a carbon coating layer and controlling the ion doping content within the aforementioned range, it is beneficial to obtain composite sodium ferrous sulfate materials with high capacity, high coulombic efficiency, and good cycle stability.

[0223] Further, in some embodiments, the composite sodium ferrous sulfate material has a D0 particle size range of 0.24 μm to 0.7 μm, a D10 particle size range of 1.0 μm to 1.9 μm, a D50 particle size range of 5 μm to 9 μm, a D90 particle size range of 10 μm to 17 μm, a D99 particle size range of 16 μm to 22 μm, and a D100 particle size range of 22 μm to 30 μm. More preferably, the composite sodium ferrous sulfate material has a D0 particle size range of 0.31 μm to 0.46 μm, a D10 particle size range of 1.0 μm to 1.46 μm, a D50 particle size range of 5 μm to 9 μm, a D90 particle size range of 11 μm to 16.8 μm, a D99 particle size range of 16.5 μm to 21.6 μm, and a D100 particle size range of 24 μm to 30 μm.

[0224] In the technical solution of this application embodiment, the particle size and distribution of the composite sodium ferrous sulfate material are within the above-mentioned range, which is beneficial to optimize the electron and ion transport path of the composite sodium ferrous sulfate material, reduce the stress between the particles of the composite sodium ferrous sulfate material, improve the electrochemical activity and capacity of the composite sodium ferrous sulfate material, and improve the structural stability and cycle stability of the composite sodium ferrous sulfate material.

[0225] Furthermore, in some embodiments, the composite sodium ferrous sulfate material is spherical, and the sphericity of the composite sodium ferrous sulfate material is 0.82 to 0.95. More preferably, the sphericity of the composite sodium ferrous sulfate material is 0.86 to 0.95.

[0226] In the technical solution of this application embodiment, the spherical composite sodium ferrous sulfate material is beneficial to reduce the voids between the composite sodium ferrous sulfate material particles, reduce stress concentration, improve the stability of the composite sodium ferrous sulfate material, and improve the cycle stability of the composite sodium ferrous sulfate material.

[0227] Furthermore, in some embodiments, the content of free sodium in the composite sodium ferrous sulfate material is less than 700 ppm. More preferably, the content of free sodium in the composite sodium ferrous sulfate material is less than 605 ppm.

[0228] In the technical solution of this application embodiment, the free sodium content is within the above range, which is beneficial to reduce the water absorption of the composite sodium ferrous sulfate material and improve the stability of the coating slurry during the preparation of the positive electrode sheet, thereby improving the electrochemical performance of the secondary battery, such as capacity and cycle stability.

[0229] Furthermore, in some embodiments, the specific surface area of ​​the composite sodium ferrous sulfate material is 7 m². 2 / g to 14m 2 / g, further, the specific surface area of ​​the composite sodium ferrous sulfate material is 7.89m². 2 / g to 13.89m 2 / g.

[0230] In the technical solutions of this application embodiment, the specific surface area is within the above-mentioned range, and the composite sodium ferrous sulfate material has a suitable number of active sites, which helps to improve the electrochemical performance of the composite sodium ferrous sulfate material, such as capacity, rate performance and coulombic efficiency.

[0231] Furthermore, in some embodiments, the powder resistivity of the composite sodium ferrous sulfate material is from 48 Ω·cm to 99 Ω·cm.

[0232] In the technical solution of this application embodiment, the powder resistivity of the composite sodium ferrous sulfate material is within the above-mentioned range. The composite sodium ferrous sulfate material has a uniformly coated carbon coating layer and uniformly distributed doped ions, which helps to reduce the electron transfer resistance and energy loss inside the secondary battery using the composite sodium ferrous sulfate material, and improve the electrochemical performance of the secondary battery such as charge and discharge efficiency, cycle stability and energy efficiency.

[0233] Furthermore, in some embodiments, the loose packing density of the composite sodium ferrous sulfate material is from 0.25 g / mL to 0.39 g / mL. More preferably, the loose packing density of the composite sodium ferrous sulfate material is from 0.26 g / mL to 0.37 g / mL.

[0234] In the technical solution of this application embodiment, the density of the composite sodium ferrous sulfate material affects the energy density and conductivity of the secondary battery. Under the above loose packing density, the secondary battery has a higher energy density and charge / discharge efficiency. Moreover, the composite sodium ferrous sulfate material has better flowability and processing performance, which facilitates the mass production of secondary batteries and improves the accuracy and efficiency of secondary battery assembly.

[0235] Furthermore, in some embodiments, the tap density of the composite sodium ferrous sulfate material is 0.7 g / mL to 0.87 g / mL, and more preferably, the tap density of the composite sodium ferrous sulfate material is 0.71 g / mL to 0.87 g / mL.

[0236] In the technical solution of this application embodiment, under the above-mentioned tap density, the secondary battery using composite sodium ferrous sulfate material has high energy density and charge / discharge efficiency.

[0237] Further, in some embodiments, the compaction density of the composite sodium ferrous sulfate material is from 2.1 g / mL to 2.37 g / mL. More preferably, the compaction density of the composite sodium ferrous sulfate material is from 2.11 g / mL to 2.37 g / mL.

[0238] In the technical solution of this application embodiment, under the above-mentioned compaction density, the secondary battery using composite sodium ferrous sulfate material has high energy density and charge / discharge efficiency.

[0239] Furthermore, in some embodiments, the mass fraction of carbon in the composite sodium ferrous sulfate material is 1.5% to 3.0%.

[0240] In the technical solutions of this application embodiment, the mass fraction of carbon element within the above range helps to improve the electronic conductivity of the composite sodium ferrous sulfate material and improve the rate performance of the composite sodium ferrous sulfate material when applied to secondary batteries.

[0241] Furthermore, in some embodiments, the lithium content in the composite sodium ferrous sulfate material is less than or equal to 68 ppm, and even further, the lithium content in the composite sodium ferrous sulfate material is less than or equal to 60 ppm, which helps to reduce side reactions during the charge and discharge process when the composite sodium ferrous sulfate material is applied to a secondary battery, thereby improving the cycle stability of the battery.

[0242] Furthermore, when the composite sodium ferrous sulfate material is applied to a secondary battery at 25°C, the initial charge specific capacity at a 0.1C rate is 80 mAh / g to 93 mAh / g, the initial discharge specific capacity at a 0.1C rate is 73 mAh / g to 83.6 mAh / g, the initial coulombic efficiency at a 0.1C rate is 88% to 92%, and the capacity retention rate at a 0.5C rate is 93% to 95.6%, demonstrating excellent electrochemical performance.

[0243] In some embodiments, the sodium ferrous sulfate material provided in this application is prepared by the lithium precipitation mother liquor recovery method described above.

[0244] Thirdly, embodiments of this application provide a positive electrode sheet comprising a composite sodium ferrous sulfate material obtained by the aforementioned lithium precipitation mother liquor recovery method or the aforementioned composite sodium ferrous sulfate material. The positive electrode sheet containing the aforementioned composite sodium ferrous sulfate material thus possesses advantages such as high capacity, high coulombic efficiency, and good cycle stability.

[0245] Fourthly, embodiments of this application provide a secondary battery including a positive electrode sheet, wherein the positive electrode sheet is the aforementioned positive electrode sheet. The secondary battery, including the aforementioned positive electrode sheet, thus possesses advantages such as high capacity, high coulombic efficiency, and good cycle stability.

[0246] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0247] I. Preparation Method

[0248] Example 1

[0249] A method for recovering lithium precipitation mother liquor includes the following steps:

[0250] Step 1: Take the lithium precipitation mother liquor, then add sulfuric acid solution to adjust the pH of the lithium precipitation mother liquor to 4.3 to obtain the first mother liquor. The concentrations of lithium, iron, sodium, and sulfate in the first mother liquor are shown in the table below.

[0251]

[0252] Step two: Add ferrous sulfate, sodium acetate, hydrazine hydrate, and boric acid to the first mother liquor to make the molar ratio of sodium, iron, and sulfate in the system 2.08:1:2.06. Stir and mix thoroughly to obtain the first mixture. The molar ratio of the added hydrazine hydrate to iron in the first mixture is 0.08:1, and the molar ratio of the added boric acid to sodium in the first mixture is 0.08:1.

[0253] Step 3: Spray dry the first mixture to obtain a first dried material with a D50 particle size of 10.5 μm and a water content (by mass percentage) of less than 1.5%.

[0254] Step 4: Place the first dried material into a roller furnace, control the furnace pressure to 150 Pa and the humidity to 0.8%, and heat it to 350 °C at a rate of 250 °C / h under a nitrogen atmosphere with an oxygen content of less than 5 ppm. Hold the temperature for 15 h to obtain the first calcined material.

[0255] The following table shows the mass percentage content of lithium, iron, sodium, sulfur, Fe(III) and carbon in the first calcined material, the sodium-iron molar ratio, the content of Al, Ca and Cd in the first calcined material, and the pH value of the first calcined material.

[0256]

[0257] Step 5: Crush the first calcined material to a particle size of 9.58 μm (D100) to obtain the crushed material.

[0258] Step 6: The pulverized material is mixed with an aqueous solution of sodium sulfite (0.15 mol / L, 60°C) at a mass ratio of 1:2 for 2 hours. The mixture is then filtered to obtain a solid material. The solid material is washed until the conductivity of the wash water is lower than 287 μS / cm to obtain the sodium ferrous sulfate precursor. The filtrate is mixed with the wash water to obtain a lithium-containing washing solution. The pH of the lithium-containing washing solution is adjusted to 9.5 to obtain a lithium-containing solution. Sodium phosphate is added to the lithium-containing solution at 75°C. The molar ratio of sodium phosphate to lithium in the lithium-containing solution is 1:2.8, and the addition time is 30 minutes. After the addition is completed, the mixture is stirred for 1.5 hours to obtain a third mixture. The third mixture is filtered, and the filter residue is washed until the conductivity of the wash water is ≤300 μS / cm. The residue is then dried to obtain lithium phosphate.

[0259] The concentrations of lithium, iron, sodium, and sulfate in the lithium-containing detergent solution, as well as the pH value of the lithium detergent solution, are shown in the table below.

[0260]

[0261] The mass percentage content of lithium and phosphorus, the content of iron, sodium, and calcium, the water content, the BET specific surface area, the D50 particle size, and the content of magnetic materials of lithium phosphate are shown in the table below.

[0262]

[0263] Step 7: Add pure water to the sodium ferrous sulfate precursor for slurry treatment to obtain a first slurry with a solid content of 30%.

[0264] Step 8: Add sucrose and ascorbic acid to the first slurry, stir and mix, then grind until the D50 particle size of the solid material is 200 nm to obtain the second slurry. The molar ratio of added ascorbic acid to iron in the second slurry is 0.035:1, and the mass ratio of added sucrose to iron is 0.775:1.

[0265] Step nine: Spray dry the second slurry to obtain a second dried material with a D50 particle size of 6.2 μm and a water content (by mass percentage) of 1.31%.

[0266] Step 10: Place the second dried material in a sintering furnace, introduce nitrogen gas to make the furnace pressure 80 Pa, oxygen content less than 1 ppm, and humidity less than 0.5%. Heat the material to 330℃ at a rate of 60℃ / h and hold for 9 hours. Then cool the material to 100℃ to obtain cooled material. The cooled material is then screened, iron removed, and packaged to obtain composite sodium ferrous sulfate material. Screening is carried out using a 150-mesh ultrasonic vibrating screen, and iron removal and packaging are carried out in a constant temperature and humidity room (humidity ≤10%, temperature 25℃).

[0267] In this embodiment, the SEM image of the first calcined material is as follows: Figure 2 As shown, the XRD pattern of the first calcined material is as follows. Figure 3 As shown, by Figure 2 and Figure 3 It can be seen that the first calcined material is spherical, and the main phase in the first calcined material is Na2Fe(SO4)2, while also containing a certain amount of Na2Fe(SO4)2·4H2O; the SEM image of the composite sodium ferrous sulfate material is shown below. Figure 4 As shown, the particles are spherical with a relatively smooth surface. The chemical formula of the composite sodium ferrous sulfate material is Na. 1.87 Fe(SO4) 1.79 (BO3) 0.108 .

[0268] Example 2

[0269] The difference between this example and Example 1 is that in step ten, the temperature is raised to 300°C for calcination. In this example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.88 Fe(SO4) 1.86 (BO3) 0.108 .

[0270] Example 3

[0271] The difference between this example and Example 1 is that in step ten, the temperature is raised to 350°C for calcination. In this example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.84 Fe(SO4) 1.72 (BO3) 0.108 .

[0272] Example 4

[0273] The difference between this example and Example 1 is that in step eight, the mass ratio of sucrose to iron is 1.1:1, resulting in a carbon mass fraction of 3% in the composite sodium ferrous sulfate material. In this example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.87 Fe(SO4) 1.79 (BO3) 0.108 .

[0274] Example 5

[0275] The difference from Example 1 is that in step eight, the mass ratio of sucrose to iron is 0.37:1, resulting in a carbon mass fraction of 1.5% in the composite sodium ferrous sulfate material. In this example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.87 Fe(SO4) 1.79 (BO3) 0.108 .

[0276] Example 6

[0277] A method for recovering lithium precipitation mother liquor includes the following steps:

[0278] Step 1: Take the lithium precipitation mother liquor, then add sulfuric acid solution to adjust the pH of the lithium precipitation mother liquor to 2, to obtain the first mother liquor. The concentrations of lithium, iron, sodium, and sulfate in the first mother liquor are shown in the table below.

[0279]

[0280] Step two: Add ferrous sulfate, sodium citrate, sodium borohydride, and phosphoric acid to the first mother liquor, making the molar ratio of sodium, iron, and sulfate in the system 2.05:1:2.02. Stir and mix thoroughly to obtain the first mixture. The molar ratio of sodium borohydride to iron in the first mixture is 0.05:1, and the molar ratio of phosphoric acid to sodium in the first mixture is 0.05:1.

[0281] Step 3: Spray dry the first mixture to obtain a first dried material with a D50 particle size of 5μm and a water content (by mass percentage) of less than 1.5%.

[0282] Step four: The first dried material is placed in a roller furnace at a furnace pressure of 20 Pa and a humidity of 0.1%. Under a nitrogen atmosphere with an oxygen content of less than 5 ppm, the temperature is increased to 300℃ at a heating rate of 200℃ / h and held for 10 hours to obtain the first calcined material. The mass percentage content of lithium, iron, sodium, sulfur, Fe(III), and carbon in the first calcined material, the sodium-iron molar ratio, the content of Al, Ca, and Cd, and the pH value of the first calcined material are shown in the table below.

[0283]

[0284] Step 5: Crush the first calcined material to a particle size of 2μm (D100) to obtain the crushed material.

[0285] Step 6: The pulverized material is mixed with an aqueous solution of 0.1 mol / L hydrazine hydrate at 40°C at a mass ratio of 1:2 for 1 hour. The mixture is then filtered to obtain a solid material. The solid material is washed until the conductivity of the wash water is below 200 μS / cm to obtain the sodium ferrous sulfate precursor. The filtrate is mixed with the wash water to obtain a lithium-containing washing solution. The pH of the lithium-containing washing solution is adjusted to 9 to obtain a lithium-containing solution. Sodium phosphate is added to the lithium-containing solution at 60°C, with a molar ratio of sodium phosphate to lithium in the lithium-containing solution of 1:2.7, over a period of 30 minutes. After addition, the mixture is stirred for 1 hour to obtain a third mixture. This third mixture is filtered, and the filter residue is washed until the conductivity of the wash water is ≤300 μS / cm. The residue is then dried to obtain lithium phosphate. The concentrations of lithium, iron, sodium, and sulfate in the lithium-containing washing solution, as well as the pH value of the lithium washing solution, are shown in the table below.

[0286]

[0287] The mass percentage content of lithium and phosphorus, the content of iron, sodium, and calcium, the moisture content, the BET specific surface area, the D50 particle size, and the content of magnetic materials of lithium phosphate are shown in the table below.

[0288]

[0289] Step 7: Add pure water to the sodium ferrous sulfate precursor for slurry treatment to obtain a first slurry with a solid content of 30%.

[0290] Step 8: Add glucose and ascorbic acid to the first slurry, stir and mix, then grind until the D50 particle size of the solid material is 100 nm to obtain the second slurry. The molar ratio of added ascorbic acid to iron in the second slurry is 0.02:1, and the mass ratio of added sucrose to iron is 0.896:1.

[0291] Step nine: Spray dry the second slurry to obtain a second dried material with a D50 particle size of 4 μm and a water content (by mass percentage) of 1.31%.

[0292] Step 10: Place the second dried material in a sintering furnace, introduce nitrogen gas to make the furnace pressure 20 Pa, oxygen content less than 1 ppm, and humidity less than 0.5%. Heat the material to 300℃ at a rate of 40℃ / h, hold for 6 hours, and then cool it to 100℃ to obtain the cooled material. The cooled material is then screened, iron removed, and packaged to obtain the composite sodium ferrous sulfate material. Screening is carried out using a 150-mesh ultrasonic vibrating screen, and iron removal and packaging are carried out in a constant temperature and humidity room (humidity ≤10%, temperature 25℃).

[0293] In this embodiment, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.79 Fe(SO4) 1.82 (PO4) 0.062 .

[0294] Example 7

[0295] A method for recovering lithium precipitation mother liquor includes the following steps:

[0296] Step 1: Take the lithium precipitation mother liquor, then add sulfuric acid solution to adjust the pH of the lithium precipitation mother liquor to 5, to obtain the first mother liquor. The concentrations of lithium, iron, sodium, and sulfate in the first mother liquor are shown in the table below.

[0297]

[0298] Step two: Add ferrous sulfate, sodium formate, sodium sulfite, and silicic acid to the first mother liquor, making the molar ratio of sodium, iron, and sulfate in the system 2.10:1:2.10. Stir and mix thoroughly to obtain the first mixture. The molar ratio of added sodium sulfite to iron in the first mixture is 0.1:1, and the molar ratio of added silicic acid to sodium in the first mixture is 0.1:1.

[0299] Step 3: Spray dry the first mixture to obtain a first dried material with a D50 particle size of 15μm and a water content (by mass percentage) of less than 1.5%.

[0300] Step four: The first dried material is placed in a roller furnace at a pressure of 300 Pa and a humidity of 1.5%. Under a nitrogen atmosphere with an oxygen content of less than 5 ppm, the temperature is increased to 400℃ at a rate of 300℃ / h and held for 20 hours to obtain the first calcined material. The mass percentage content of lithium, iron, sodium, sulfur, Fe(III), and carbon in the first calcined material, the molar ratio of sodium to iron, the content of Al, Ca, and Cd, and the pH value of the first calcined material are shown in the table below.

[0301]

[0302] Step 5: Crush the first calcined material to a particle size of 5μm (D100) to obtain the crushed material.

[0303] Step 6: The pulverized material is mixed with a 0.2 mol / L sodium sulfite aqueous solution at 80°C at a mass ratio of 1:2 for 3 hours. The mixture is then filtered to obtain a solid material, which is washed until the conductivity of the wash water is below 300 μS / cm to obtain the sodium ferrous sulfate precursor. The filtrate is mixed with the wash water to obtain a lithium-containing washing solution. The pH of the lithium-containing washing solution is adjusted to 10.5 to obtain a lithium-containing solution. Sodium phosphate is added to the lithium-containing solution at 90°C at a molar ratio of 1:2.9 to the lithium in the solution, over a period of 30 minutes. After addition, the mixture is stirred for 2 hours to obtain a third mixture. This third mixture is filtered, and the filter residue is washed until the conductivity of the wash water is ≤300 μS / cm. The residue is then dried to obtain lithium phosphate. The concentrations of lithium, iron, sodium, and sulfate in the lithium-containing washing solution, as well as the pH value of the lithium washing solution, are shown in the table below.

[0304]

[0305] The mass percentage content of lithium and phosphorus, the content of iron, sodium, and calcium, the water content, the BET specific surface area, the D50 particle size, and the content of magnetic materials of lithium phosphate are shown in the table below.

[0306]

[0307] Step 7: Add pure water to the sodium ferrous sulfate precursor for slurry treatment to obtain a first slurry with a solid content of 40%.

[0308] Step 8: Add water-soluble starch and phosphorous acid to the first slurry, stir and mix, then grind until the D50 particle size of the solid material is 300 nm to obtain the second slurry. The molar ratio of added phosphorous acid to iron in the second slurry is 0.05:1, and the mass ratio of added sucrose to iron is 1.1:1.

[0309] Step nine: Spray dry the second slurry to obtain a second dried material with a D50 particle size of 10 μm and a water content (by mass percentage) of 1.31%.

[0310] Step 10: Place the second dried material in a sintering furnace, introduce nitrogen gas to make the furnace pressure 200 Pa, oxygen content less than 1 ppm, and humidity less than 0.5%. Heat the material to 350 °C at a rate of 80 °C / h, hold for 12 h, and then cool it to 100 °C to obtain the cooled material. The cooled material is then screened, iron removed, and packaged to obtain the composite sodium ferrous sulfate material. Screening is carried out using a 150-mesh ultrasonic vibrating screen, and iron removal and packaging are carried out in a constant temperature and humidity room (humidity ≤10%, temperature 25 °C).

[0311] In this embodiment, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.82 Fe(SO4) 1.94 (SiO4) 0.131 .

[0312] Example 8

[0313] The difference from Example 1 is that in step two, the amount of reducing agent hydrazine hydrate added is reduced, so that the molar ratio of the added hydrazine hydrate to the iron element in the first mixture is 0.05:1. In this example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.90 Fe(SO4) 1.82 (BO3) 0.111 .

[0314] Example 9

[0315] The difference from Example 1 is that in step two, the amount of boric acid dopant added is increased, so that the molar ratio of the added boric acid to sodium in the first mixture is 0.1:1. In this example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.87 Fe(SO4) 1.79 (BO3) 0.135 .

[0316] Example 10

[0317] The difference from Example 1 is that, in step two, the amount of boric acid dopant added is increased, so that the molar ratio of the added boric acid to sodium in the first mixture is 0.2:1. In this example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.88 Fe(SO4) 1.79 (BO3) 0.271 .

[0318] Example 11

[0319] The difference from Example 1 is that the dopant boric acid in step two is replaced with phosphoric acid. In this example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.87 Fe(SO4) 1.79 (PO4) 0.108 .

[0320] Example 12

[0321] The difference between this example and Example 1 is that the dopant boric acid in step two is replaced with silicic acid. In this example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.87 Fe(SO4) 1.79 (SiO4) 0.108 .

[0322] Example 13

[0323] The difference between this example and Example 1 is that the dopant boric acid in step two is replaced with pyrophosphate. In this example, the chemical formula of the composite sodium ferrous sulfate is Na. 1.87 Fe(SO4) 1.79 (P2O7) 0.054 .

[0324] Example 14

[0325] The difference between this example and Example 1 is that boric acid, a dopant, was not added in step two. In this example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.57 Fe(SO4) 1.79 .

[0326] Example 15

[0327] The difference from Example 1 is that in step two, the amount of reducing agent hydrazine hydrate added is increased, so that the molar ratio of the added hydrazine hydrate to the iron element in the first mixture is 0.1:1. In this example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.85 Fe(SO4) 1.73 (BO3) 0.106 .

[0328] Example 16

[0329] The difference from Example 1 is that in step two, the amount of reducing agent hydrazine hydrate is reduced, so that the molar ratio of the added hydrazine hydrate to the iron element in the first mixture is 0.02:1. In this example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.86 Fe(SO4) 1.81 (BO3) 0.109 .

[0330] Comparative Example 1

[0331] The difference between this and Example 1 is that in step two, the amount of ferrous sulfate is increased so that the molar ratio of sodium, iron and sulfate in the system is 2:1:2.30.

[0332] The following table shows the mass percentage content of lithium, iron, sodium, sulfur, Fe(III) and carbon in the first calcined material, the sodium-iron molar ratio, the content of Al, Ca and Cd in the first calcined material, and the pH value of the first calcined material.

[0333]

[0334] In this comparative example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.91 Fe(SO4) 1.97 (BO3) 0.108 .

[0335] Comparative Example 2

[0336] The difference between this example and Example 1 is that, in step six, the 0.15 mol / L sodium sulfite aqueous solution is replaced with pure water, and ascorbic acid is not added in step eight. In this comparative example, the chemical formula of the composite sodium ferrous sulfate material is Na. 1.65 Fe(SO4) 1.75 (BO3) 0.108 .

[0337] II. Testing Methods

[0338] 1. Material property testing

[0339] 1) The morphology of the material was characterized using scanning electron microscopy (SEM).

[0340] 2) The material composition was characterized by X-ray diffraction.

[0341] 3) The elemental composition of the materials was analyzed using inductively coupled plasma atomic emission spectrometry (ICP-AES). Table 1 shows the mass percentages of lithium, iron, sodium, carbon, and dopant ions, as well as the content of lithium impurities, in the composite ferrous sulfate materials prepared in the examples and comparative examples.

[0342] 4) pH value test: The test was conducted in accordance with GB / T 9724, General Rules for pH Value Determination of Chemical Reagents. The pH value of the surface of the composite ferrous sulfate material is shown in Table 1.

[0343] 5) Free sodium content test: The free sodium content in the composite ferrous sulfate materials prepared in the examples and comparative examples was determined by potentiometric titration. The percentage of free sodium by mass in the samples is shown in Table 1.

[0344] 6) Compaction density test: The compaction density of the material was tested using a compaction density meter. The test pressure was 3T and the pressing time was 30S. The compaction density of the composite ferrous sulfate material prepared in the examples and comparative examples is shown in Table 1.

[0345] 7) Specific surface area test: The specific surface area of ​​the materials was tested using the nitrogen adsorption BET test method, referring to the standard GB / T9587-2017. The specific surface area test results of the composite ferrous sulfate materials prepared in the examples and comparative examples are shown in Table 1.

[0346] 8) Loose packing density test: The loose packing density of the composite ferrous sulfate material prepared in the examples and comparative examples is shown in Table 1, referring to GB / T 31057.1-2014 and using the funnel method.

[0347] 9) Tap density test: The tap density was tested using a tap density meter with 5000 vibrations. The tap density of the composite ferrous sulfate materials prepared in the examples and comparative examples is shown in Table 1.

[0348] 10) The particle size (μm) of the material was tested using a laser particle size analyzer. The test results of the D0, D10, D50, D90, D99 and D100 particle sizes are shown in Table 2.

[0349] 11) Sphericity test: A combination of microscopic measurement methods and image processing technology is used. The particle images are processed and analyzed by image analysis software to obtain the particle size and shape information of each particle. Then, the particle size and shape information of each particle are statistically analyzed to obtain the particle size and particle size distribution, average aspect ratio and aspect ratio distribution, average roundness and roundness distribution, etc. Here, the average roundness is used to represent the sphericity of the sodium ferrous sulfate material. The results are shown in Table 2.

[0350] 12) Powder resistivity test: The four-probe method is used for testing, and the test pressure is 10 MPa.

[0351] 2. Properties of secondary batteries

[0352] 1) Battery assembly

[0353] The composite sodium ferrous sulfate material prepared in the examples and comparative examples was mixed with SP and PVDF binders at a mass ratio of 92:4:4. After homogenization, the mixture was coated onto aluminum foil, dried at 100°C, and then rolled using a roller press. A positive electrode sheet with a diameter of 14 mm was then obtained using a stamping machine. The mass of the active material was obtained by weighing and deducting the mass of the aluminum foil.

[0354] After drying the positive electrode, a sodium sheet is used as the negative electrode. The coin cell is assembled in the following order: negative electrode shell, sodium sheet, electrolyte (0.1M NaPF6 as solute, and a mixed solution of ethylene carbonate, dimethyl carbonate, and diethyl carbonate in a volume ratio of 1:1:1 as solvent), separator, electrolyte, positive electrode, gasket, spring, and positive electrode shell, in the UNlab type inert gas glove box of Braun GmbH, Germany.

[0355] 2) Charge and discharge performance test

[0356] The electrical performance of coin cells at 0.1C was tested using the Wuhan Landian CT2001A battery testing system. The voltage range was 2V to 4.50V, and the test temperature was 25℃. The test results for the 0.1C initial charge capacity, 0.1C initial discharge capacity, and 0.1C initial coulombic efficiency are shown in Table 3.

[0357] 3) Cyclic performance test

[0358] The coin cells were subjected to cyclic charge-discharge tests using the Wuhan Landian CT2001A battery testing system. The cyclic charge-discharge conditions were as follows: constant current charging at 0.5C to 4.5V, then constant voltage charging to 0.01C, resting for 5 minutes, constant current discharging at 0.5C to 2.00V, resting for 5 minutes, and then repeating the charge-discharge cycle. The capacity retention rate of each battery after 500 cycles is shown in Table 3.

[0359] III. Analysis of Test Results for Each Embodiment and Comparative Example

[0360] Note: "-" in the table indicates that it is the same as in Example 1.

[0361] Table 1

[0362]

[0363] Table 2

[0364]

[0365] Table 3

[0366]

[0367] From Tables 1 to 3 and Figure 5As can be seen from the embodiments, the lithium precipitation mother liquor recovery method in this application achieves effective separation and recovery of lithium ions and sodium ions, while realizing efficient and high-value-added utilization of sodium, lithium, and sulfate ions. Furthermore, the recovered composite sodium ferrous sulfate material, due to the prior preparation of its precursor followed by secondary carbon coating, exhibits more uniform carbon coating and higher compaction density. Simultaneously, anion composite doping significantly improves the ionic conductivity of the composite sodium ferrous sulfate material, resulting in high capacity, high initial coulombic efficiency, and good cycle performance. In addition, the lithium precipitation mother liquor recovery method in the embodiments yields high-purity lithium phosphate.

[0368] Furthermore, the results corresponding to Examples 1, 9 and 10 in Tables 1 to 3 show that when the molar ratio of the dopant to sodium in the first mixture is (0.05~0.1):1, the composite sodium ferrous sulfate material exhibits better cycling performance.

[0369] As can be seen from the results corresponding to Examples 1, 8, 15 and 16 in Tables 1 to 3, when the molar ratio of the reducing agent to the iron element in the first mixture is (0.05~0.1):1, it is more conducive to improving the electrochemical performance of the composite sodium ferrous sulfate material, such as the initial coulombic efficiency and cycle stability.

[0370] As can be seen from the corresponding results of Examples 1 and 14 in Tables 1 to 3, adding dopants to the first mixture helps to improve the electrochemical performance of the composite sodium ferrous sulfate material, such as the first charge specific capacity, the first discharge specific capacity, the first coulombic efficiency, and the cycle stability.

[0371] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A lithium sink liquor recovery method characterized by, The method comprises the following steps: adjusting the pH value of the lithium precipitation mother liquor to less than or equal to 5 to obtain a first mother liquor; mixing the first mother liquor with ferrous sulfate, a sodium salt, and a first reducing agent to obtain a first mixture; subjecting the first mixture to a first drying treatment to obtain a first dried material; subjecting the first dried material to a first calcination treatment to obtain a first calcined material; subjecting the first calcined material to a crushing treatment to obtain a crushed material; mixing the crushed material with an aqueous solution of a second reducing agent, and then subjecting the mixture to a solid-liquid separation treatment to obtain a sodium ferrous sulfate precursor; subjecting the sodium ferrous sulfate precursor to a slurry treatment to obtain a first slurry; mixing the first slurry, a carbon source, and a third reducing agent, and then subjecting the mixture to a grinding treatment to obtain a second slurry; subjecting the second slurry to a second drying treatment to obtain a second dried material; subjecting the second dried material to a second calcination treatment to obtain a composite sodium ferrous sulfate material; In the first mixture, the molar ratio of sodium, iron, and sulfate is (2.05-2.10):1:(2.02-2.10); The first calcination treatment is carried out in a first protective atmosphere; The second calcination treatment is carried out in a second protective atmosphere.

2. The lithium sink liquor recovery method of claim 1, wherein, The first mixture also includes a dopant selected from at least one of boric acid, phosphoric acid, silicic acid, and pyrophosphoric acid, and the molar ratio of the dopant to sodium in the first mixture is (0.05-0.1):

1.

3. The lithium precipitation mother liquor recovery method according to claim 1 or 2, characterized in that: The step of adjusting the pH value of the lithium precipitation mother liquor to less than or equal to 5 comprises: adding sulfuric acid solution to the lithium precipitation mother liquor until the pH value of the lithium precipitation mother liquor is 2-5; The step of subjecting the first dried material to a first calcination treatment to obtain a first calcined material comprises: The first dried material is subjected to a first calcination treatment for a first calcination time under a first protective atmosphere and at a first calcination temperature to obtain the first calcined material; wherein the first protective atmosphere is selected from one or more of a nitrogen atmosphere, a carbon dioxide atmosphere, and an argon atmosphere, the first calcination temperature is 300-400°C, and the first calcination time is 10-20h; The step of mixing the crushed material with an aqueous solution of a second reducing agent, and then subjecting the mixture to a solid-liquid separation treatment to obtain a sodium ferrous sulfate precursor comprises: mixing the crushed material with the aqueous solution of the second reducing agent at a first mixing temperature for a first mixing time to obtain a second mixture; The second mixture is subjected to a solid-liquid separation to obtain a solid material, and the solid material is washed until the conductivity of the washing water is less than or equal to 300μS / cm to obtain the sodium ferrous sulfate precursor; The first mixing time is 1-3h, and the first mixing temperature is 40-80°C; The step of subjecting the second dried material to a second calcination treatment to obtain a composite sodium ferrous sulfate material comprises: The second dry material is calcined under the second protective atmosphere, at a second calcination temperature, for a second calcination time, to obtain the composite sodium ferrous sulfate material; wherein the second protective atmosphere is selected from one or more of a nitrogen atmosphere, a carbon dioxide atmosphere, and an argon atmosphere, the second calcination temperature is 300-350°C, and the second calcination time is 6-12 hours.

4. The lithium sink liquor recovery method of claim 3, wherein, The second calcination process further comprises: The calcined material obtained by calcining the second dry material under the second protective atmosphere, at the second calcination temperature, for the second calcination time, is cooled to a temperature of less than or equal to 100°C, to obtain a cooled material; The cooled material is sequentially subjected to screening and iron removal, to obtain the composite sodium ferrous sulfate material.

5. The lithium sink liquor recovery method according to claim 1 or 2, characterized in that, The lithium sink mother liquor recovery method has at least one of the following characteristics: (1) The molar ratio of the first reducing agent to the iron element in the first mixture is (0.05-0.1):1; (2) The D50 particle size of the first dry material is 5-15 μm; (3) The water content in the first dry material is less than 1.5% by mass percentage; (4) The D100 particle size of the crushed material is less than or equal to 10 μm; (5) In the aqueous solution of the second reducing agent, the concentration of the second reducing agent is 0.1-0.2 mol / L; (6) The dispersion medium of the first slurry is water, and the solid content of the first slurry is 30-40% by mass percentage; (7) In the second slurry, the D50 particle size of the solid material is 100-300 nm; (8) In the second slurry, the mass ratio of the carbon source to the iron element is (0.35-1.2):1; (9) In the second slurry, the molar ratio of the third reducing agent to the iron element is (0.02-0.05):1; (10) The D50 particle size of the second dry material is 4-10 μm; (11) The water content in the second dry material is less than 1.5% by mass percentage.

6. The lithium sink liquor recovery method according to claim 1 or 2, characterized in that, The lithium sink mother liquor recovery method has at least one of the following characteristics: (1) The first reducing agent is selected from at least one of hydrazine hydrate, sodium borohydride, and sodium sulfite; (2) The sodium salt is selected from at least one of sodium bicarbonate, sodium acetate, sodium citrate, sodium formate, and sodium benzoate; (3) The second reducing agent is selected from at least one of hydrazine hydrate and sodium sulfite; (4) The carbon source is selected from at least one of glucose, sucrose, PEG, and water-soluble starch; (5) The third reducing agent is selected from at least one of ascorbic acid and phosphorous acid.

7. A composite ferrous sulfate sodium material characterized in that, The composite ferrous sulfate sodium material comprises sodium ferrous sulfate and a carbon coating layer at least partially coating the surface of the sodium ferrous sulfate; the sodium ferrous sulfate has a general formula of Na X Fe (SO4) Y C W , X is in a range of 1.57-1.90, Y is in a range of 1.72-1.94, and W is in a range of 0-0.271; C is selected from at least one of borate, phosphate, silicate and pyrophosphate; the mass fraction of carbon in the composite ferrous sulfate sodium material is 1.5%-3%; the composite ferrous sulfate sodium material is spheroid-like; and the composite ferrous sulfate sodium material is recovered by the lithium recovery mother liquor recovery method in any one of claims 1-6.

8. The composite ferrous sulfate sodium material of claim 7, wherein, The composite sodium ferrous sulfate material has at least one of the following characteristics: (1) The D50 particle size of the composite sodium ferrous sulfate material is in the range of 5-9 μm, and the D100 particle size is in the range of 22-30 μm; (2) The sphericity of the composite sodium ferrous sulfate material is 0.82-0.95; (3) The content of free sodium element in the composite sodium ferrous sulfate material is less than 700 ppm; (4) the specific surface area of the composite ferrous sulfate sodium material is 7 m 2 / g to 14 m 2 / g; (5) The powder resistivity of the composite sodium ferrous sulfate material is 48-99 Ω·cm; (6) the bulk density of the composite ferrous sulfate sodium material is 0.25 g / mL to 0.39 g / mL; (7) the tap density of the composite ferrous sulfate sodium material is 0.7 g / mL to 0.87 g / mL; (8) the compacted density of the composite ferrous sulfate sodium material is 2.1 g / mL to 2.37 g / mL.

9. A positive electrode sheet characterized by comprising: The positive electrode plate comprises the composite ferrous sulfate sodium material obtained by the lithium precipitation mother liquor recovery method according to any one of claims 1 to 6 or the composite ferrous sulfate sodium material according to claim 7 or 8.

10. A secondary battery comprising a positive electrode sheet, characterized by, The positive electrode plate is the positive electrode plate according to claim 9.

Citation Information

Patent Citations

  • Carbon-coated sodium ferrous sulfate phosphate positive electrode material as well as preparation method and application thereof

    CN119447266A